Resist underlayer film forming method and pattern forming method
By using multi-layer resist method and plasma irradiation technology in semiconductor manufacturing, a resist lower layer film containing aromatic ring resin is formed, which solves the problem of microresizing of the photoresist film and achieves high-precision fine patterns Improved transfer and dry etch resistance.
Patent Information
- Application Number
- CN202410890067.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-07
- Filing Date
- 2024-07-04
- Publication Date
- 2025-01-07
AI Technical Summary
Prior Art In the manufacturing of semiconductor devices, fine refinement of the photoresist film leads to a decrease in resolution performance, pattern collapse and dry etch resistance are insufficient, making it difficult to achieve high-precision fine pattern transfer.
By using the multi-layer resist method, a resist lower layer film containing aromatic ring resin is formed on the substrate and cured by plasma irradiation. Combined with dry etching technology, a resist lower layer with excellent dry etching resistance is formed. Films to achieve high-precision pattern transfer.
The dry etching resistance and pattern transfer accuracy of the resist lower layer film are significantly improved, and are suitable for large and fine pattern structures with high aspect ratios, avoiding pattern collapse and hollow formation, ensuring flatness characteristics and landfill effects.
Smart Images

Figure CN119270590A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resist underlayer film forming method and a pattern forming method. More specifically, the present invention relates to a resist underlayer film forming method applicable to fine patterning by a multilayer resist method in a semiconductor device manufacturing process and a pattern forming method using the resist underlayer film. Background Art
[0002] With the high integration and high speed of LSI, the pattern size is being miniaturized rapidly. With this miniaturization, photolithography technology realizes the formation of fine patterns by shortening the wavelength of the light source and appropriately selecting the resist composition. The focus is on the positive photoresist composition used in the form of a single layer. The single-layer positive photoresist composition has a skeleton with etching resistance to dry etching based on chlorine or fluorine gas plasma in the resist resin, and has a switching mechanism such that the exposed part dissolves, so that the exposed part dissolves to form a pattern, and the residual resist pattern is used as an etching mask to perform dry etching processing on the processed substrate.
[0003] However, if the thickness of the photoresist film used is directly miniaturized, that is, if the pattern width is further reduced, the resolution performance of the photoresist film will be reduced. In addition, when the photoresist film is intended to be patterned with a developer, the so-called aspect ratio becomes too large, resulting in a problem of pattern collapse. Therefore, as the pattern is miniaturized, the photoresist film begins to be thinner.
[0004] On the other hand, in the processing of the processed substrate, a method of processing the substrate by dry etching is usually used to form a photoresist film with a pattern as an etching mask, but in reality, there is no dry etching method that can obtain complete etching selectivity between the photoresist film and the processed substrate. Therefore, there is the following problem: in the processing of the substrate, the photoresist film is also damaged and collapsed, and the resist pattern cannot be accurately transferred to the processed substrate. Therefore, with the miniaturization of the pattern, a higher dry etching resistance is required for the resist composition. However, on the other hand, in order to improve the definition, for the resin used in the photoresist composition, a resin with small light absorption under the exposure wavelength is required. Therefore, as the exposure light is i-ray, KrF, ArF and the wavelength is shortened, the resin is also changed to a novolac resin, polyhydroxystyrene, and a resin with an aliphatic polycyclic skeleton. But in reality, the etching speed under the dry etching conditions during substrate processing gradually becomes faster, and the current photoresist composition with high definition has a tendency to weaken etching resistance.
[0005] Therefore, it is necessary to perform dry etching processing on the substrate to be processed using a thinner photoresist film with weaker etching resistance, and ensuring the materials and process in this processing step has become a top priority.
[0006] As one of the methods to solve this problem, there is a multilayer resist method. This method is as follows: a resist intermediate film having an etching selectivity different from that of a photoresist film (i.e., a resist upper film) is sandwiched between the resist upper film and a substrate to be processed, and after the resist upper film is patterned, the resist upper film pattern is used as a dry etching mask to transfer the pattern to the resist intermediate film by dry etching, and further, the resist intermediate film is used as a dry etching mask to transfer the pattern to the substrate to be processed by dry etching.
[0007] One of the multilayer resist methods is a three-layer resist method that can be performed using a general resist composition used in a single-layer resist method. In the three-layer resist method, for example, an organic film based on a novolac resin or the like is formed on a processed substrate as a resist lower film, a silicon-containing resist intermediate film is formed thereon as a resist intermediate film, and a conventional organic photoresist film is formed thereon as a resist upper film. When dry etching is performed using fluorine-based gas plasma, the organic resist upper film achieves a good etching selectivity ratio for the silicon-containing resist intermediate film, and therefore, the resist upper film pattern can be transferred to the silicon-containing resist intermediate film by dry etching based on fluorine-based gas plasma. According to this method, even if a resist composition that is difficult to form a pattern having a sufficient film thickness for directly processing a substrate to be processed is used, or a resist composition that does not have sufficient dry etching resistance for processing a substrate is used, a pattern can be transferred to a silicon-containing resist intermediate film (resist intermediate film), and if the pattern is subsequently transferred by dry etching based on oxygen or hydrogen gas plasma, a pattern based on an organic film (resist underlayer film) such as a novolac resin having sufficient dry etching resistance for processing a substrate can be obtained. As the resist underlayer film as described above, various underlayer films such as the underlayer film described in Patent Document 1 are already known.
[0008] On the other hand, in recent years, the miniaturization of DRAM memory has been accelerating, and the need for further improvement of dry etching resistance and resist underlayer films with excellent filling and planarization characteristics has gradually increased. As coating-type organic underlayer film materials with excellent filling and planarization characteristics, for example, the material described in Patent Document 2 has been reported, but when considering the application in the next generation, there are concerns about dry etching resistance, and the existing coating-type organic underlayer film materials are close to the application limit.
[0009] In order to solve the above-mentioned problem, Patent Document 3 reports that the etching resistance of the resist underlayer film during substrate processing is improved by subjecting the resist underlayer film to plasma irradiation or electron beam irradiation. However, the resist underlayer film used in the above-mentioned embodiments mostly contains a resin or compound containing a hydroxyl group or a propargyl group, and a cross-linking reaction also occurs competitively during plasma irradiation or electron beam irradiation. Therefore, it is predicted that the modification of the resist underlayer film is insufficient. In addition, it is considered that since oxygen atoms remain in the film, it is not preferable from the viewpoint of etching resistance.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2004-205685
[0013] Patent Document 2: Japanese Patent Application Publication No. 2017-119671
[0014] Patent Document 3: Japanese Patent Application Publication No. 2020-183506 Summary of the invention
[0015] Problem that the invention aims to solve
[0016] The present invention has been made in view of the above circumstances, and its object is to provide a resist underlayer film forming method capable of forming a resist underlayer film showing extremely excellent dry etching resistance with respect to existing organic underlayer film materials, and a pattern forming method using the resist underlayer film forming method.
[0017] Solutions for solving problems
[0018] In order to solve the above-mentioned problems, the present invention provides a method for forming a resist underlayer film, characterized in that it is a method for forming a resist underlayer film on a substrate, comprising the following steps:
[0019] (i) a step of applying a resist underlayer film-forming composition comprising (A) a polymer and an organic solvent onto the substrate to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. to 800° C. for 10 seconds to 7,200 seconds to cure the coating film, thereby forming an underlayer film precursor film; and
[0020] (ii) a step of curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film,
[0021] As the polymer (A), an aromatic ring-containing resin is used which does not contain a hydroxyl group and an organic group represented by the following general formula (1) in the repeating unit constituting the polymer.
[0022]
[0023] (In the above general formula (1), p is 0 or 1, and * is a bonding part.)
[0024] If this resist underlayer film forming method is used, the film can be easily modified by plasma irradiation, and a resist underlayer film having excellent dry etching resistance can be provided. When a hydroxyl group or an organic group represented by the general formula (1) is included, thermal curing is actively performed, so that the number of active sites modified by plasma irradiation in the film decreases, which is not preferred.
[0025] As the aromatic ring-containing resin, it is preferable to use the polymer (A) containing a structure selected from the group consisting of structures represented by the following formula (1-1).
[0026]
[0027] When a resin having the above structure is used, the film can be modified more easily by plasma irradiation, and a resist underlayer film having more excellent dry etching resistance can be provided.
[0028] The polymer (A) preferably has any one of the structural units represented by the following general formulae (A-1), (A-2), (A-3), (A-4) and (A-5).
[0029]
[0030] (In the above general formula (A-1), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1).)
[0031]
[0032] (In the above general formula (A-2), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms which does not contain a hydroxyl group and an organic group represented by the above general formula (1); Ar2 is a fused aromatic ring different from Ar1, which is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms which does not contain a hydroxyl group and an organic group represented by the above general formula (1).)
[0033]
[0034] (In the above general formula (A-3), R1 is any one of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms.)
[0035]
[0036] (In the above general formula (A-4), R2 is any one of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms.)
[0037]
[0038] (In the above general formula (A-5), R1 represents a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1), and Ar3 and Ar4 are each an unsubstituted benzene ring or a naphthalene ring.)
[0039] By using a composition containing a resin having any of the structural units represented by the general formulae (A-1) to (A-5), the dry etching resistance after plasma irradiation can be further improved.
[0040] As the polymer (A), it is preferred to use a polymer having a molecular weight of 300 to 5,000 in terms of polystyrene based on gel permeation chromatography.
[0041] According to the resist underlayer film forming method using the resist underlayer film forming composition containing a resin having a weight average molecular weight within such a range, outgassing during baking can be suppressed without impairing solubility in organic solvents.
[0042] As the resist underlayer film-forming composition, it is preferable to use a composition further containing one or more of (C) a crosslinking agent, (D) a surfactant, (E) an acid generator, and (F) a plasticizer.
[0043] By using the resist underlayer film-forming composition containing the above additives, various physical properties required for forming a resist underlayer film, such as coating properties, dry etching resistance, and filling / planarization characteristics, can be adjusted within appropriate ranges.
[0044] In this case, as the cross-linking agent (C), it is preferable to use a cross-linking agent having a structure represented by the following general formula (C-1).
[0045]
[0046] (In the above general formula (C-1), W1 and W2 are each a benzene ring or a naphthalene ring which may have a substituent, R2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any one of the groups represented by the following general formula (2).)
[0047]
[0048] When the composition contains a crosslinking agent having a structure represented by the general formula (C-1), the resist underlayer film after plasma irradiation can provide excellent film thickness uniformity.
[0049] In the above-mentioned step (ii), the above-mentioned plasma irradiation can be carried out in an atmosphere of N2, NF3, H2, fluorocarbons, rare gases or a mixture of any of them.
[0050] By using the above method as the curing method for the resist underlayer film, it is possible to provide a resist underlayer film that exhibits excellent dry etching resistance compared to a curing method that only involves heating.
[0051] In the step (i), the heat treatment may be performed in an atmosphere having an oxygen concentration of 1% to 21%.
[0052] By this method, the reaction sites of the resin in the resist underlayer film precursor film can be activated, and the curing reaction by plasma irradiation can be promoted.
[0053] Alternatively, in the step (i), the heat treatment may be performed in an atmosphere having an oxygen concentration of less than 1%.
[0054] This method is useful because even when the processed substrate contains a raw material that is unstable to heating in an oxygen atmosphere, the processed substrate will not be degraded, the reaction sites of the resin in the resist underlayer precursor film can be activated, and the curing reaction based on plasma irradiation can be promoted.
[0055] In addition, the present invention provides a pattern forming method, characterized in that it is a method for forming a pattern on a processed substrate, comprising the following steps:
[0056] (I-1) a step of forming a resist underlayer film on a substrate to be processed by the resist underlayer film forming method of the present invention;
[0057] (I-2) a step of forming a resist intermediate film on the resist underlayer film;
[0058] (I-3) a step of forming a resist upper layer film on the resist intermediate film using a photoresist material;
[0059] (I-4) a step of exposing the resist upper layer film to pattern exposure and then developing the resist upper layer film with a developer to form a pattern on the resist upper layer film;
[0060] (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film having the pattern as a mask;
[0061] (I-6) a step of transferring the pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern is transferred as a mask; and
[0062] (I-7) A step of processing the substrate to be processed using the resist underlayer film having the pattern formed thereon as a mask to form a pattern on the substrate to be processed.
[0063] According to the above-described pattern forming method, a resist underlayer film having excellent dry etching resistance can be used, and therefore a fine pattern can be formed with high precision on a substrate as a workpiece.
[0064] Effects of the Invention
[0065] As described above, according to the resist underlayer film forming method of the present invention, a resist underlayer film that exhibits extremely excellent dry etching resistance with respect to existing organic underlayer film materials can be formed.
[0066] Furthermore, according to the pattern forming method of the present invention, a fine pattern can be formed with high precision on a substrate as a workpiece.
[0067] Furthermore, the resist lower film forming method and pattern forming method of the present invention are particularly suitable for multilayer resist processes including embedding / planarization of processed substrates with height differences and concave-convex surfaces, and are extremely useful in the fine patterning for manufacturing semiconductor devices. In particular, in the fine patterning process using the multilayer resist method in the semiconductor device manufacturing process, even on the processed substrate with a dense portion of a fine pattern structure with a high aspect ratio represented by a gradually miniaturized DRAM memory, which is difficult to embed / planarize, it is possible to embed without producing defects such as pores and peeling, and a resist lower film with excellent flat characteristics can be formed. In addition, the existing resist lower film forming method shows excellent etching resistance, especially by plasma irradiation, so that its effect can be exerted. Therefore, a fine pattern can be formed on the processed body with higher precision. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 It is an explanatory diagram of an example (three-layer resist process) of the pattern forming method of the present invention.
[0069] Figure 2 This is a diagram for explaining the landfill characteristics evaluation method.
[0070] Description of Reference Numerals
[0071] 1…support substrate, 1A…processed substrate, 2…processed layer, 2a…pattern (pattern formed in the processed layer), 3…resist lower layer film, 3a…resist lower layer film pattern, 4…resist intermediate film, 4a…resist intermediate film pattern, 5…resist upper layer film, 5a…resist upper layer film pattern, 6…exposure portion, 7…base substrate having dense lines & spaces, 8…resist lower layer film. DETAILED DESCRIPTION
[0072] As described above, there is a demand for developing a pattern forming method capable of transferring a resist pattern to a substrate to be processed with higher accuracy in a fine patterning process using a multilayer resist method, and a forming method capable of forming a resist underlayer film useful in such a pattern forming method.
[0073] Patent document 3 reports that by plasma irradiation, the dry etching resistance of the resist lower film during substrate processing is improved. It can be inferred that by plasma irradiation, the carbon bonds of the resist lower film will separate and rebond, and reconstruct in the form of a cured film with a diamond-like carbon structure, thereby contributing to the increase of hardness and density. On the other hand, it can be inferred that the resist lower film forming composition used in the embodiment of patent document 3 contains a hydroxyl group and an organic group shown in the above general formula (1), so that not only the separation and rebonding of carbon bonds occur, but also a cross-linking reaction occurs competitively. Therefore, the present inventors believe that the film modification based on plasma irradiation may not be fully performed.
[0074] The present inventors have been searching for a resist underlayer film forming method in which separation and recombination of carbon bonds are actively generated by plasma irradiation, and have repeatedly conducted intensive studies. As a result, they have found that a resist underlayer film showing extremely excellent dry etching resistance compared to the conventional resist underlayer film forming method based on plasma irradiation can be formed by the following underlayer film forming method, which includes the following steps: a step of applying a resist underlayer film forming composition containing an aromatic ring-containing resin ((A) polymer) that does not contain a hydroxyl group and an organic group represented by the above general formula (1) and an organic solvent, and subjecting the obtained coating film to heat treatment at a temperature of 100° C. to 800° C. for 10 seconds to 7,200 seconds to cure it, thereby forming an underlayer film precursor film; and a step of curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film, thereby completing the present invention.
[0075] That is, the present invention is a method for forming a resist underlayer film, characterized in that it is a method for forming a resist underlayer film on a substrate, comprising the following steps:
[0076] (i) a step of applying a resist underlayer film-forming composition comprising (A) a polymer and an organic solvent onto the substrate to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. to 800° C. for 10 seconds to 7,200 seconds to cure the coating film, thereby forming an underlayer film precursor film; and
[0077] (ii) a step of curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film,
[0078] As the polymer (A), an aromatic ring-containing resin is used which does not contain a hydroxyl group and an organic group represented by the following general formula (1) in the repeating unit constituting the polymer.
[0079]
[0080] (In the above general formula (1), p is 0 or 1, and * is a bonding part.)
[0081] In addition, the present invention is a method for forming a pattern, characterized in that it is a method for forming a pattern on a substrate to be processed.
[0082] (I-1) a step of forming a resist underlayer film on a substrate to be processed by the resist underlayer film forming method of the present invention;
[0083] (I-2) a step of forming a resist intermediate film on the resist underlayer film;
[0084] (I-3) a step of forming a resist upper layer film on the resist intermediate film using a photoresist material;
[0085] (I-4) a step of exposing the resist upper layer film to pattern exposure and then developing the resist upper layer film with a developer to form a pattern on the resist upper layer film;
[0086] (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film having the pattern as a mask;
[0087] (I-6) a step of transferring the pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern is transferred as a mask; and
[0088] (I-7) A step of processing the substrate to be processed using the resist underlayer film having the pattern formed thereon as a mask to form a pattern on the substrate to be processed.
[0089] Hereinafter, the present invention will be described in detail, but the present invention is not limited to these.
[0090] <Resist Underlayer Film Formation Method>
[0091] The present invention is a method for forming a resist underlayer film, characterized in that it is a method for forming a resist underlayer film on a substrate, comprising the following steps:
[0092] (i) a step of applying a resist underlayer film-forming composition comprising (A) a polymer and an organic solvent onto the substrate to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. to 800° C. for 10 seconds to 7,200 seconds to cure the coating film, thereby forming an underlayer film precursor film; and
[0093] (ii) a step of curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film,
[0094] As the polymer (A), an aromatic ring-containing resin is used which does not contain a hydroxyl group and an organic group represented by the following general formula (1) in the repeating unit constituting the polymer.
[0095]
[0096] (In the above general formula (1), p is 0 or 1, and * is a bonding part.)
[0097] If this resist underlayer film forming method is used, a resist underlayer film having excellent dry etching resistance during substrate processing can be formed. More specifically, if this resist underlayer film forming method is used, film modification can be easily generated by plasma irradiation, and a resist underlayer film having excellent dry etching resistance can be formed.
[0098] The method for applying the resist underlayer film-forming composition in the step (i) is not particularly limited. The details of the resist underlayer film-forming composition will be described later.
[0099] In the above step (i), the heat treatment (baking) temperature of the coating film is set to a temperature of 100°C to 800°C, more preferably 150°C to 600°C, and even more preferably 150°C to 400°C. The baking time is set to a range of 10 seconds to 7,200 seconds, and even more preferably 30 seconds to 600 seconds.
[0100] By appropriately adjusting the baking temperature and time within the above range, it is possible to obtain planarization / burying characteristics suitable for the application, as well as curing characteristics such as dry etching resistance and heat resistance. By performing heat treatment (baking) in a temperature range of more than 150°C and less than 400°C, a state in which a large number of active points for separation and rebonding of carbon bonds in the lower film precursor film are present in the film is presented, which easily promotes film modification based on plasma irradiation, and thus, a resist lower film with excellent dry etching resistance can be formed. At a baking temperature of more than 100°C, the residual solvent in the film can be reduced, and the degradation of the film thickness uniformity caused by plasma irradiation can be suppressed. If the baking temperature is set to less than 800°C, the thermal decomposition of the base resin can be suppressed, and a resist lower film with a small amount of sublimates can be provided. The heat treatment can also be performed in multiple times (stage baking).
[0101] In the step (i) above, the heat treatment may be performed in an atmosphere having an oxygen concentration of 1% to 21%.
[0102] By this method, the reaction sites of the resin in the resist underlayer film precursor film can be activated, and the curing reaction by plasma irradiation can be promoted.
[0103] Alternatively, in the step (i) above, the heat treatment may be performed in an atmosphere having an oxygen concentration of less than 1%.
[0104] As the baking atmosphere, any of an oxygen-containing atmosphere such as air (oxygen concentration is 1% to 21%) and a non-oxygen atmosphere such as nitrogen can be selected as needed. For example, when the substrate to be processed is easily oxidized by air, a cured film can be formed by heat treatment in an atmosphere with an oxygen concentration of less than 1%, thereby suppressing damage to the substrate.
[0105] Plasma irradiation can be performed by a known method, for example, the method described in Japanese Patent No. 5746670, "Improvement of the wiggling profile of spin-on carbon hard mask by H2 plasma treatment" (J. Vac. Sci. Technol. B26 (1), Jan / Feb 2008, p67-71).
[0106] The RF discharge power is preferably 100 to 10,000W, more preferably 500 to 5,000W.
[0107] As the gas atmosphere, for example, rare gases such as N2, NF3, H2, and He, and fluorocarbon compounds can be listed; more preferably, He, Ar, N2, Ne, NF3, H2, CF4, CHF3, CH2F2, CH3F, C4F6, C4F8, etc. can be listed. Two or more of these gases can be used in combination. It is an advantage of the present invention that the effect of the present invention can be expected even when a gas atmosphere containing no O2 is used.
[0108] The plasma irradiation time can be selected from, for example, 10 to 240 seconds, and the pressure can be appropriately selected.
[0109] In the above step (ii), the plasma irradiation is preferably performed in an atmosphere of a rare gas such as N2, NF3, H2, fluorocarbons, He, or a mixture of any of them.
[0110] From the viewpoint of productivity, particularly preferred gas atmospheres include He, Ar, N 2 , and H 2 .
[0111] After plasma irradiation, the resist lower film may be subjected to heat treatment. When heating is performed after plasma irradiation, as heating conditions, the heating temperature may be appropriately selected from the range of 80 to 800° C. (preferably 100 to 700° C., more preferably 200 to 600° C.), and the heating time may be appropriately selected from the range of 30 to 180 seconds (preferably 30 to 120 seconds). Although not bound by theory, it can be considered that by performing high-temperature heating after plasma irradiation, the dangling bonds are bonded, which can contribute to the high density of the cured film (resist lower film).
[0112] As the atmosphere for heating after plasma irradiation, any of an oxygen-containing atmosphere such as air (oxygen concentration is 1% to 21%) and a non-oxygen atmosphere such as nitrogen can be selected as needed. For example, in the case where the substrate to be processed is easily oxidized by air, a cured film can be formed by heat treatment in an atmosphere with an oxygen concentration of less than 1%, thereby suppressing damage to the substrate.
[0113] The irradiation device is not particularly limited as long as it can perform plasma irradiation, and for example, Telius SP and Tactras Vigus manufactured by Tokyo Electron Limited can be used. The device can be selected and the conditions can be set so that the effects of the present invention can be more significantly exhibited.
[0114] In the pattern forming method of the present invention using the resist underlayer film forming composition described in detail below, it is preferred to use a processed substrate with a structure or height difference of more than 30nm. The resist underlayer film forming composition used in the present invention has excellent filling / planarization characteristics, so even if the processed substrate has a structure or height difference (concave-convex) with a height of more than 30nm, a flat resist underlayer film (cured film) can be formed. The height of the structure or height difference possessed by the above-mentioned processed body substrate is preferably more than 30nm, more preferably more than 50nm, and more preferably more than 100nm. In the method for processing the height difference substrate of the pattern with the above-mentioned height, the resist underlayer film is formed by utilizing the resist underlayer film forming method of the present invention and buried / planarized, so that the film thickness of the resist intermediate film and the resist upper film formed thereafter can be uniform, therefore, it is easy to ensure the exposure depth margin (DOF) during photolithography, which is very preferred.
[0115] <Resist Underlayer Film-Forming Composition>
[0116] In the resist underlayer film forming method of the present invention, a resist underlayer film forming composition comprising (A) a polymer and an organic solvent is used, and as the aforementioned polymer, an aromatic ring-containing resin is used which does not contain a hydroxyl group and an organic group represented by the following general formula (1) in the repeating units constituting the aforementioned polymer.
[0117]
[0118] (In the above general formula (1), p is 0 or 1, and * is a bonding part.)
[0119] [(A) Polymer (resin)]
[0120] By using an aromatic ring-containing resin that does not contain a hydroxyl group and an organic group represented by the general formula (1) in the repeating units constituting the above-mentioned polymer as the above-mentioned (A) polymer, it is easy to modify the resist underlayer film by plasma irradiation, thereby forming a resist underlayer film with excellent etching resistance during substrate processing.
[0121] The (A) polymer is preferably a resin including a structure selected from the group consisting of structures represented by the following formula (1-1).
[0122]
[0123] By including the condensed aromatic ring having a high carbon density as described above, the resist underlayer precursor film can be easily modified by plasma irradiation, and a resist underlayer film having more excellent dry etching resistance during substrate processing can be formed.
[0124] The polymer (A) is preferably a resin having at least one of the structural units represented by the following general formulae (A-1) to (A-5).
[0125] (Structural units: A-1 and A-2)
[0126]
[0127] (In the above general formula (A-1), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1).)
[0128]
[0129] (In the above general formula (A-2), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms which does not contain a hydroxyl group and an organic group represented by the above general formula (1); Ar2 is a fused aromatic ring different from Ar1, which is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms which does not contain a hydroxyl group and an organic group represented by the above general formula (1).)
[0130] If the resin has any structural unit represented by the above-mentioned general formula (A-1) and (A-2), a condensed aromatic ring with a high carbon density is introduced. Therefore, the separation and re-bonding of carbon bonds can be easily promoted by plasma irradiation, and a resist underlayer film having a diamond-like carbon structure can be formed.
[0131] Specific examples of the structures of Ar1 and Ar2 include the following structures (A-1a), but are not limited to these.
[0132]
[0133] (In the above formula (A-1a), R A1 It is a divalent organic group having 1 to 20 carbon atoms, or a hydrogen atom, which does not contain a hydroxyl group and the organic group represented by the above general formula (1).
[0134] If Ar1 and Ar2 are polymers having any condensed aromatic ring represented by the above-mentioned general formula (A-1a), a composition for forming an anti-etching underlayer film having excellent solvent solubility can be prepared. Since the condensed aromatic ring has a high carbon density, the separation and re-bonding of carbon bonds can be easily promoted by plasma irradiation, thereby forming an anti-etching underlayer film having a diamond-like carbon structure.
[0135] In the above formula (A-1a), R A1It is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms (excluding a hydroxyl group and an organic group represented by the above general formula (1)), more preferably a hydrogen atom, an alkyl group having 1 to 20 carbon atoms (excluding a hydroxyl group and an organic group represented by the above general formula (1)), a phenyl group or a benzyl group, and further preferably a hydrogen atom.
[0136] If Ar1 and Ar2 are groups R A1 A group containing will not deteriorate the dry etching resistance and can further improve the solvent solubility, so it is preferred.
[0137] From the viewpoint of solvent solubility and productivity of the aromatic ring-containing resin (A), the following structures can be exemplified as particularly preferred structures among the structures represented by the above-mentioned general formula (A-1a).
[0138]
[0139] (In the above formula, R A1 It is a divalent organic group having 1 to 20 carbon atoms, or a hydrogen atom, which does not contain a hydroxyl group or an organic group represented by the above general formula (1).
[0140] The polymer having the structure represented by the above formula (A-1) may be a copolymer having two types of repeating units represented by the following formula (A-1x).
[0141]
[0142] (In the above formula (A-1x), Ar1' is any one of naphthalene, anthracene, phenanthrene or pyrene, Ar2' is a structure different from Ar1', and is selected from any one of the above formula (A-1a). a+b is 100, 30≤a≤99, 1≤b≤70.)
[0143] In the above formula (A-1x), Ar1' is any one of naphthalene, anthracene, phenanthrene or pyrene. From the viewpoint of easily promoting the separation and recombination of carbon bonds during high temperature treatment under a nitrogen atmosphere and being able to form a film of amorphous carbon, naphthalene and anthracene are preferred, and anthracene is more preferred. In addition, in the above formula (2), Ar2' is a structure different from Ar1'. When Ar1' is anthracene, Ar2' is preferably naphthalene, phenanthrene or pyrene from the viewpoint of etching resistance, solvent solubility and productivity.
[0144] In the above formula (A-1x), the ranges of a and b are 30≤a≤99 and 1≤b≤70, and preferably 50≤a≤80 and 20≤b≤50 from the viewpoint of etching resistance and solvent solubility.
[0145] A polymer randomly having two different repeating units like the above formula (A-1x) is preferred because the solvent solubility can be further improved.
[0146] In the general formula (A-2), either Ar1 or Ar2 is preferably anthracene. By including an anthracene structure, separation and recombination of carbon bonds can be easily promoted by plasma irradiation, and a resist underlayer film having a diamond-like carbon structure can be formed.
[0147] The resin having the structural unit represented by the above general formula (A-1) and (A-1x) may have an end-capping group represented by the following general formula (W-1). It should be noted that the following end-capping group is not included in the repeating unit constituting the polymer.
[0148]
[0149] (In the above formula (W-1), * is a bonding portion that bonds to the structural unit represented by the above formula (A-1) or formula (A-2), d is an integer of 1 to 9, and e is an integer of 0 to 2.)
[0150] By having such a blocking group, the solvent solubility and substrate adhesion of the resin can be further improved.
[0151] In the above formula (W-1), d is an integer of 1 to 9, and e is an integer of 0 to 2. From the viewpoint of etching resistance, solvent solubility and substrate adhesion, it is preferred that d is 1 or 2 and e is 0 or 1. When it is desired to improve etching resistance, it is preferred that d is small and e is large. When it is desired to improve solvent solubility / substrate adhesion, it is preferred that d is large and e is small.
[0152] The molecular weight of the polymer having the structural units represented by the above-mentioned general formula (A-1) and (A-2) in terms of polystyrene conversion based on gel permeation chromatography is preferably 300 to 5,000, and more preferably 500 to 3,500. When it is above 300, the amount of sublimated products can be suppressed, and the degradation of the uniformity of the film thickness can be suppressed. When it is below 5,000, the solvent solubility of the resin can be maintained, and precipitation over time can be prevented, so it is preferred from the viewpoint of storage stability. In addition, due to the excellent fluidity, excellent filling properties and excellent flatness can be achieved. In addition, outgassing during baking can be suppressed without impairing the solubility of the aforementioned polymer in an organic solvent.
[0153] [First method for producing a polymer]
[0154] The resin having the structure represented by formula (A-1) as a repeating unit can be obtained, for example, by a polycondensation reaction of a condensed aromatic ring compound represented by Ar1 shown below and aldehyde. Ar1 in the following formula is the same as described above.
[0155]
[0156] The condensed aromatic ring compound or aldehyde compound used in the polycondensation reaction may be used alone or in combination of two or more kinds, and these may be appropriately selected and combined depending on the required properties.
[0157] The polycondensation reaction can be carried out in an organic solvent and in the presence of an acid catalyst at room temperature or under cooling or heating as required. As the acid catalyst used, inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropolyacids can be listed; organic acids such as oxalic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid; Lewis acids such as aluminum chloride, aluminum ethoxide, aluminum isopropoxide, boron trifluoride, boron trichloride, boron tribromide, tin tetrachloride, tin tetrabromide, dibutyltin dichloride, dibutyltin dimethanolate, dibutyltin oxide, titanium tetrachloride, titanium tetrabromide, titanium (IV) methoxide, titanium (IV) ethoxide, titanium (IV) isopropoxide, and titanium (IV) oxide.
[0158] Examples of the organic solvent used in the polycondensation reaction include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, methyl ethyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, and hexamethylphosphorotriamide. These solvents can be used alone or in combination of two or more.
[0159] As the reaction method, there are the following methods: a method of adding the condensed aromatic ring compound together with the aldehyde compound and the acid catalyst; a method of dispersing or dissolving the condensed aromatic ring compound and the aldehyde compound and then adding the acid catalyst together or diluting with a solvent and then adding dropwise; or a method of dispersing or dissolving the acid catalyst and then adding the condensed aromatic ring compound and the aldehyde compound together or diluting with a solvent and then adding dropwise. After the reaction is completed, it can be used directly in the composition for forming an organic film of the present invention, or it can be recovered by diluting with an organic solvent and washing for removing unreacted raw materials, acid catalysts, etc. in the system.
[0160] The organic solvent used in the liquid separation and cleaning is not particularly limited as long as it can dissolve the compound and separate into two layers when mixed with water. Examples thereof include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, and methyl isobutyl ketone; ethers such as diethyl ether, diisopropyl ether, methyl tert-butyl ether, and ethyl cyclopentyl methyl ether; chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; and mixtures thereof.
[0161] As the washing water used in the liquid separation washing, deionized water or ultrapure water can be generally used. The washing frequency can be 1 or more, but since the effect corresponding to the washing frequency may not be obtained even if the washing frequency is 10 or more, it is preferably 1 to 5 times.
[0162] During the liquid separation and cleaning, in order to remove the unreacted raw materials or acidic components in the system, an alkaline aqueous solution can be used for cleaning. Specifically, the alkali contained in the alkaline aqueous solution includes alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia and organic ammonium.
[0163] Furthermore, during the liquid separation and cleaning, in order to remove the unreacted raw materials, metal impurities or alkaline components in the system, an acidic aqueous solution can be used for cleaning. Specifically, the acid contained in the acidic aqueous solution includes inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropoly acids; and organic acids such as oxalic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.
[0164] The liquid separation washing using the alkaline aqueous solution and the acidic aqueous solution may be performed alone or in combination. From the viewpoint of removing metal impurities, the liquid separation washing is preferably performed in the order of the alkaline aqueous solution and the acidic aqueous solution.
[0165] After the liquid separation and cleaning based on the above-mentioned alkaline aqueous solution and acidic aqueous solution, neutral water can be used for cleaning. As for the number of cleanings, it only needs to be performed once or more, preferably about 1 to 5 times. As neutral water, deionized water, ultrapure water, etc. described above can be used. The number of cleanings only needs to be once or more. When the number of cleanings is small, the alkaline component and the acidic component may not be removed. Even if the cleaning is performed more than 10 times, the effect corresponding to the number of cleanings may not be obtained, so it is preferably about 1 to 5 times.
[0166] Furthermore, the reaction product after liquid separation and washing can also be concentrated and dried or crystallized under reduced pressure or normal pressure to recover the solvent in the form of powder. In order to improve the operability when preparing the organic film-forming composition, it can also be prepared in advance into a solution state of appropriate concentration. As the concentration at this time, it is preferably 0.1 to 50% by weight, and more preferably 0.5 to 30% by weight. If it is such a concentration, the viscosity is not easy to increase, so it can prevent the operability from being impaired, and in addition, the amount of solvent will not be too large, so it becomes economical.
[0167] The solvent in this case is not particularly limited as long as it can dissolve the polymer. Specific examples include ketones such as cyclohexanone and methyl-2-pentyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono-tert-butyl ether acetate. These may be used alone or in combination of two or more.
[0168] [Second method for producing a polymer (other method 1)]
[0169] As a second manufacturing method of another method, a resin having a structure represented by formula (A-1) as a repeating unit can also be obtained by a polymerization reaction using a raw material represented by Ar1-CH2-X. Ar1 is the same as above, and X is a hydroxyl group, an alkoxy group having 1 to 4 carbon atoms, or a halogen group.
[0170]
[0171] The polymerization reaction described above becomes the polymerization reaction that can utilize the monomer itself to obtain a polymer. In the polycondensation reaction of the first manufacturing method, two common monomers A and B are used, and a polymer having a form of repeating units derived from monomers A and B is formed by dehydration reaction between molecules, etc. If it is the manufacturing method of the above-mentioned polymer, a homopolymer can be synthesized using one monomer. In the present invention, from the viewpoint of productivity, the second manufacturing method is preferably used.
[0172] [First method for producing a polymer: monomers alternately form repeating units]
[0173]
[0174] [Second method for producing a polymer (other method 1): homopolymer formed only from monomer A]
[0175]
[0176] In the case of the synthetic reaction method of the polymer shown above, when two monomers (Ar1 and Ar2) with different multiple fused aromatic rings are used as an example, as long as the monomers are added together, a random polymer (A-1x) without a specific repeating unit can be synthesized. In addition, after synthesizing the polymer using a monomer having Ar1 in the first stage, a monomer having Ar2 is further added in the second stage, thereby synthesizing a polymer having a block structure. These synthetic methods can be appropriately selected according to the required performance, etc.
[0177]
[0178] [2 types of monomers: random type (added together)]
[0179]
[0180] [2 types of monomers: block type (two-stage injection)]
[0181]
[0182] Since the polymer represented by the formula (A-1x) obtained by the above synthesis method randomly contains two types of repeating units, a resin having more excellent solvent solubility can be provided.
[0183] Furthermore, if it is the second synthesis reaction method of the polymer shown above, it is also possible to import or introduce an aromatic component Arx (there is no reactive unit in Arx) that can react with the monomer as an end-capping unit during the reaction. The method for introducing these end-capping groups can be appropriately selected according to the reaction rate, etc. In the first polymerization method, due to the reactivity, it is only possible to introduce to both ends, but when using this polymerization method, it is possible to introduce one molecule of end-capping units into one molecule of polymer. Therefore, when introducing polar groups such as hydroxyl groups that adjust the film-forming properties and adhesion when used as a resist lower film material based on the end-capping, it is possible to use the minimum amount of introduction to achieve performance improvement, which is advantageous from the perspective of etching resistance. On the other hand, when the repeating unit structure of the polymer contains a hydroxyl group or an organic group shown in the above general formula (1), the polymer contains a large amount of cross-linking group components, so the separation / rebonding and curing reaction of the carbon bond based on plasma irradiation will occur competitively, and there is a risk of damage to the modification of the film with excellent dry etching resistance.
[0184] [End-capping: introduced during the reaction]
[0185]
[0186] [Capping: Put in together]
[0187]
[0188] As the aromatic component Arx, the following components can be exemplified, and these aromatic rings may optionally have substituents such as vinyl, ethynyl, ethynylphenyl, allyl, propargyl, aryl, allyloxy and propargyloxy. From the viewpoint of imparting etching resistance and solvent solubility, the above-mentioned substituents preferably have a naphthalene ring, a fluorene structure, or a carbazole structure.
[0189]
[0190]
[0191]
[0192] [Third method for producing a polymer (an example of a method for producing a resin having a structure represented by formula (A-2) as a repeating unit) (Other method 2)]
[0193] The polymer (resin) having the structure represented by the above formula (A-2) as a repeating unit can be obtained by a polymerization reaction using a condensed aromatic ring compound represented by Ar1 and a raw material represented by X-CH2-Ar2-CH2-X as shown below.
[0194]
[0195] (Ar1 and Ar2 are the same as above, and X is a hydroxyl group, an alkoxy group having 1 to 4 carbon atoms, or a halogen group.)
[0196] The polymer obtained by the third manufacturing method (a resin containing the structure represented by formula (A-2) as a repeating unit) becomes a polymer having repeating units in which a condensed aromatic ring compound and X-CH2-Ar2-CH2-X are alternately arranged.
[0197] [Monomers A and B alternate to form repeating units]
[0198]
[0199] The second and third synthesis reactions of the polymer differ from the first production method only in the monomers used, and the same reaction method and recovery method as those described in the description of the first production method can be implemented.
[0200] (Structural units: A-3 and A-4)
[0201]
[0202] (In the above general formula (A-3), R1 is any one of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms.)
[0203] In the above general formula (A-3), from the viewpoint of raw material availability, R1 is preferably a hydrogen atom.
[0204]
[0205] (In the above general formula (A-4), R2 is any one of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms.)
[0206] In the above general formula (A-4), from the viewpoint of raw material availability, R2 is preferably a hydrogen atom.
[0207] If the resin has the structural units represented by the above-mentioned general formulae (A-3) and (A-4), an aromatic ring with a high carbon density is introduced. Therefore, the separation and recombination of carbon bonds are easily promoted by plasma irradiation, and a resist underlayer film having a diamond-like carbon structure can be formed.
[0208] The polymer used in the present invention may be a resin containing both the structural units represented by the above-mentioned general formulae (A-3) and (A-4), and may further contain a resin having a structural unit represented by the following general formula (A-4a).
[0209]
[0210] Preferred examples of the resins composed of the general formulae (A-3), (A-4) and (A-4a) include resins having a structure represented by the following general formula (1C).
[0211]
[0212] (In the above general formula (1C), a, b and c are respectively in the range of a+b+c=1, 0.5≤a≤0.9, and 0.1≤b+c≤0.5.)
[0213] In the above general formula (1C), a, b and c are preferably in the range of a+b+c=1, 0.5≤a≤0.9, 0.1≤b+c≤0.5, and more preferably in the range of 0.7≤a≤0.9, 0.1≤b+c≤0.3.
[0214] Regarding the specific structure of the resin having the structures represented by the above-mentioned general formulas (A-3) and (A-4), there is no particular limitation as long as these structures are contained in the resin. It can be a mixed composition of a resin having a structural unit represented by the general formula (A-3) and a resin having a structural unit represented by the general formula (A-4), or it can be a copolymer of a resin having a structural unit represented by the general formula (A-3) and a resin having a structural unit represented by the general formula (A-4).
[0215] The aforementioned polymer can be obtained by polymerizing a polymerizable monomer using a known method. When obtaining a polymer, each monomer protected by a protecting group can be polymerized as required, and then a deprotection reaction can be performed as required, thereby synthesizing a polymer. As a reaction method for obtaining a polymer, there is no particular limitation, and methods such as free radical polymerization and cationic polymerization can be used, and appropriate selection can be made according to the reactivity of the monomers.
[0216] In the case of using free radical polymerization, there is a method of mixing monomers having polymerizable unsaturated bonds, adding a free radical initiator to a solvent for heat polymerization, thereby obtaining a polymer. The polymerization conditions can be variously selected according to the monomers used, the target molecular weight, etc., and as the solvent used in the polymerization, specifically, toluene, benzene, tetrahydrofuran, diethyl ether, dioxane, 2-butanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, cyclohexanone, γ-butyrolactone, ethyl acetate, butyl acetate can be exemplified. As a polymerization initiator, 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile), dimethyl 2,2-azobis(2-methylpropionate), benzoyl peroxide, lauroyl peroxide, etc. can be exemplified. In addition, during the polymerization, as a chain transfer agent, thiols such as octanethiol and 2-mercaptoethanol can be added. The polymerization reaction can be preferably heated to 40°C to the boiling point of the reaction solvent for carrying out. The reaction time is 0.5 to 100 hours, preferably 1 to 48 hours.
[0217] In the case of using cationic polymerization, there is a method of mixing monomers having polymerizable unsaturated bonds, adding a cationic polymerization initiator and polymerizing, thereby obtaining a polymer. The polymerization conditions can be selected in various ways according to the monomers used, the target molecular weight, etc., and as the solvent used in the polymerization, specifically, hexane, heptane, octane, toluene, dichloromethane, 1,2-dichloroethane, diethyl ether, butyl ether, etc. can be exemplified. As a catalyst used as a cationic polymerization initiator, proton acids such as hydrochloric acid, sulfuric acid, perchloric acid, trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid, chlorosulfonic acid, and fluorosulfonic acid can be used; Lewis acids such as boron trifluoride, aluminum chloride, titanium tetrachloride, tin chloride, and ferric chloride can be used. In the case of using a Lewis acid as a catalyst, if there is a proton supply source such as an acid, water, or alcohol in an amount equivalent to the catalyst, the cationic polymerization activity will increase, so it can be added. The polymerization reaction is not particularly limited as long as the temperature at which the reaction is carried out, and it can be preferably heated to -10°C to the boiling point of the reaction solvent. The reaction time is 0.5 to 100 hours, preferably 1 to 48 hours.
[0218] The method for obtaining the above-mentioned polymer is preferably cationic polymerization. In free radical polymerization, a terminal structure containing heteroatoms such as oxygen and nitrogen other than carbon, which may deteriorate etching resistance, is introduced into the polymer due to a free radical initiator, but this disadvantage does not exist in cationic polymerization. Therefore, from the viewpoint of etching resistance, cationic polymerization is preferably used as a method for obtaining the polymer.
[0219] The molecular weight of the resin having any structural unit represented by the above-mentioned general formula (A-3) and (A-4) in terms of polystyrene conversion based on gel permeation chromatography is preferably 300 to 5,000, more preferably 1,000 to 4,500, and further preferably 2,000 to 4000. When it is above 300, the amount of sublimated products can be suppressed, and the degradation of the uniformity of the film thickness can be suppressed. When it is below 5,000, the solvent solubility of the resin can be maintained and precipitation over time can be prevented, so it is preferred from the viewpoint of storage stability. In addition, due to the excellent fluidity, excellent filling properties and excellent flatness can be achieved. In addition, outgassing during baking can be suppressed without impairing the solubility of the aforementioned polymer in an organic solvent.
[0220] (Structural unit: A-5)
[0221]
[0222] (In the above general formula (A-5), R1 represents a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1), and Ar3 and Ar4 are each an unsubstituted benzene ring or a naphthalene ring.)
[0223] In the general formula (A-5), the partial structure composed of Ar3 and Ar4 may be exemplified by the following partial structures. Among the following partial structures, fluorene and benzofluorene structures are preferred from the viewpoint of easy availability of raw materials.
[0224]
[0225] The polymer preferably further has a partial structure represented by the following general formula (A-5a).
[0226]
[0227] (In the above general formula (A-5a), Q1 is an alkoxy group having 1 to 10 carbon atoms, or an organic group having one or more aromatic rings which may have substituents other than a hydroxyl group and an organic group represented by the above general formula (1), R1 is a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms which does not contain a hydroxyl group and an organic group represented by the above general formula (1), and Ar3 and Ar4 are unsubstituted benzene rings or naphthalene rings.)
[0228] As the organic group having one or more aromatic rings in Q1 in the general formula (A-5a), the following organic groups can be exemplified, and these aromatic rings may optionally have substituents such as alkyl, aryl, ethynylphenyl, etc. From the viewpoint of imparting etching resistance and solvent solubility, the aforementioned organic group preferably has a naphthalene ring, a fluorene structure, or a carbazole structure.
[0229]
[0230]
[0231]
[0232] In the present invention, it is preferred that the polymer further has a partial structure represented by (A-5b).
[0233]
[0234] (In the above general formula (A-5b), Q2 represents a hydrogen atom or a monovalent organic group having 1 to 50 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1), and Ar3 and Ar4 are as described above.)
[0235] As Q2 in the general formula (A-5b), an alkyl group having 1 to 10 carbon atoms or the following structure can be exemplified. When Q2 has an aromatic ring, the aromatic ring may optionally have a substituent such as an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an ethynylphenyl group, an aryl group, etc. Among these, a naphthyl group is preferred from the viewpoint of imparting etching resistance and solvent solubility.
[0236]
[0237]
[0238] As a method for synthesizing the above-mentioned polymer, the method described in paragraphs
[0059] to
[0079] of Japanese Patent No. 7082087 can be used.
[0239] The molecular weight of the resin having the structural unit represented by the above general formula (A-5) in terms of polystyrene conversion based on gel permeation chromatography is preferably 300 to 5,000, and more preferably 600 to 4,000. When it is above 300, the amount of sublimation can be suppressed, and the degradation of the uniformity of the film thickness can be suppressed. When it is below 5,000, the solvent solubility of the resin can be maintained and precipitation over time can be prevented, so it is preferred from the viewpoint of storage stability. In addition, due to the excellent fluidity, excellent filling properties and excellent flatness can be achieved. In addition, outgassing during baking can be suppressed without damaging the solubility of the aforementioned polymer in an organic solvent.
[0240] [(B) Organic solvent]
[0241] The organic solvent that can be used in the resist underlayer film-forming composition is not particularly limited as long as it can dissolve the polymer (A), but is preferably an organic solvent that can also dissolve the crosslinking agent, surfactant, acid generator, and plasticizer described below.
[0242] Specifically, for example, the solvents described in paragraphs
[0091] to
[0092] of Japanese Patent Application Laid-Open No. 2007-199653 may be added. More specifically, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, cyclopentanone, cyclohexanone and γ-butyrolactone, or a mixture containing one or more of these is preferably used.
[0243] The amount of the organic solvent added is preferably adjusted according to the desired film thickness of the resist underlayer film, and is usually in the range of 100 to 50,000 parts by mass based on 100 parts by mass of the (A) polymer.
[0244] [(B-1) High boiling point solvent]
[0245] In addition, in the above-mentioned resist underlayer film forming composition, (B) the organic solvent can be used in the form of a mixture of one or more organic solvents having a boiling point lower than 180 degrees and one or more organic solvents having a boiling point higher than 180 degrees (hereinafter referred to as "(B-1) high boiling point solvent").
[0246] Specific examples of the organic solvent having a boiling point of less than 180 degrees include propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, cyclopentanone, and cyclohexanone.
[0247] The high boiling point solvent (B-1) is not particularly limited to hydrocarbons, alcohols, ketones, esters, ethers, chlorine-based solvents, and the like as long as it can dissolve the components of the resist underlayer film forming composition used in the present invention. Specific examples thereof include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl- 1,3-Hexanediol, Diethylene Glycol, Dipropylene Glycol, Triethylene Glycol, Tripropylene Glycol, Glycerol, Nonyl Acetate, Monohexyl Ether, Ethylene Glycol Mono-2-ethylhexyl Ether, Ethylene Glycol Monophenyl Ether, Ethylene Glycol Monobenzyl Ether, Diethylene Glycol Monoethyl Ether, Diethylene Glycol Monoisopropyl Ether, Diethylene Glycol Mono-n-butyl Ether, Diethylene Glycol Monoisobutyl Ether, Diethylene Glycol Monohexyl Ether, Diethylene Glycol Monophenyl Ether, Diethylene Glycol Monobenzyl Ether, Diethylene Glycol Diethyl Ether, Diethylene Glycol Dibutyl Ether, Diethylene Glycol Butyl Methyl Ether, Triethylene Glycol Dimethyl Ether, triethylene glycol monomethyl ether, triethylene glycol n-butyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol di Acetate, dipropylene glycol methyl n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate and dibutyl adipate, etc., which can be used alone or in combination.
[0248] (B-1) The high boiling point solvent can be appropriately selected from, for example, the above-mentioned solvents according to the temperature at which the above-mentioned resist underlayer film-forming composition is heat-treated. The boiling point of the high boiling point solvent (B-1) is preferably 180°C to 300°C, and more preferably 200°C to 300°C. If it is such a boiling point, there is no need to worry about volatilization too fast during baking (heat treatment) due to the boiling point being too low, so that sufficient thermal fluidity can be obtained during film formation. In addition, if it is such a boiling point, there is no situation where the boiling point is too high and does not volatilize after baking and remains in the film, so there is no need to worry about adverse effects on film properties such as etching resistance.
[0249] In addition, the amount of the high boiling point solvent (B-1) when used is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, relative to 100 parts by mass of the resin represented by the general formula (A). If it is such an amount, there is no need to worry that the amount is too small and sufficient thermal fluidity cannot be given during baking, or that the amount is too large and remains in the film and causes the film properties such as etching resistance to deteriorate, which is preferred.
[0250] [(C) Cross-linking agent]
[0251] Furthermore, a crosslinking agent (C) may be added to the resist underlayer film-forming composition in order to improve curability and dry etching resistance.
[0252] Specifically, as the cross-linking agent (C), a compound having a structure represented by the following general formula (C-1) is particularly preferred.
[0253]
[0254] (In the above general formula (C-1), W1 and W2 are each a benzene ring or a naphthalene ring which may have a substituent, R2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any one of the groups represented by the following general formula (2).)
[0255]
[0256] By including the crosslinking agent (C), the crosslinking density and hardness of the resist underlayer film can be further increased without deteriorating the dry etching resistance of the resist underlayer film-forming composition.
[0257] The ratio Mw / Mn of the polystyrene-equivalent weight average molecular weight Mw and the number average molecular weight Mn of the cross-linking agent (C) is preferably 1.00≤Mw / Mn≤1.25.
[0258] If the molecular weight dispersion of the cross-linking agent is as described above, the thermal fluidity of the resist underlayer film forming composition becomes good. Therefore, when it is mixed with the resist underlayer film material, it can not only well fill the fine structure formed on the substrate but also form a resist underlayer film with a flat substrate as a whole.
[0259] As other (C) crosslinking agents, there are no particular limitations, and crosslinking agents of various well-known systems can be widely used. As an example, melamine crosslinking agents, glycoluril crosslinking agents, benzoguanamine crosslinking agents, urea crosslinking agents, β-hydroxyalkylamide crosslinking agents, isocyanurate crosslinking agents, aziridine crosslinking agents, oxazoline crosslinking agents, epoxy crosslinking agents, phenol crosslinking agents (such as hydroxymethyl or alkoxymethyl crosslinking agents of polynuclear phenols) can be illustrated. The amount of the crosslinking agent added is preferably 5 to 100 parts by mass, more preferably 10 to 50 parts by mass, relative to 100 parts by mass of the resin represented by the general formula (A).
[0260] As melamine-based crosslinking agents, specifically, hexamethoxymethylated melamine, hexabutoxymethylated melamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As glycoluril-based crosslinking agents, specifically, tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As benzoguanamine-based crosslinking agents, specifically, tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As urea-based crosslinking agents, specifically, dimethoxymethylated dimethoxyethylene urea, its alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As β-hydroxyalkylamide-based crosslinking agents, specifically, N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide can be exemplified. Specific examples of isocyanurate crosslinking agents include triglycidyl isocyanurate and triallyl isocyanurate. Specific examples of aziridine crosslinking agents include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tert-butyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymers. Specific examples of the epoxy crosslinking agent include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.
[0261] Specific examples of the polynuclear phenol-based crosslinking agent include compounds represented by the following general formula (C-2).
[0262]
[0263] (In the formula, Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R3 is a hydrogen atom or a methyl group. q is an integer of 1 to 5.)
[0264] Q in the general formula (C-2) is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. q is an integer of 1 to 5, and more preferably 2 or 3. When Q is a q-valent hydrocarbon group having 1 to 20 carbon atoms, Q is a q-valent hydrocarbon group obtained by removing q hydrogen atoms from a hydrocarbon having 1 to 20 carbon atoms. More specifically, examples of the hydrocarbon having 1 to 20 carbon atoms include methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane.
[0265] R3 in the above general formula (C-2) is a hydrogen atom or a methyl group, and is preferably a methyl group.
[0266] By including the compound represented by the general formula (C-2) as the cross-linking agent (C), the density of the film can be improved, thereby further improving the heat resistance of the resist underlayer film-forming composition.
[0267] As examples of compounds represented by the above general formula (C-2), specifically, the following compounds can be illustrated, but are not limited to them. In the following formula, R3 is the same as above. When q=3 is satisfied and R3 is a hydrogen atom or a methyl group, it is preferred from the viewpoint of improving curability, uniformity of film thickness and reducing sublimates, and particularly preferred are trisphenolmethane, trisphenolethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and hexamethoxymethylated forms of tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene.
[0268]
[0269]
[0270] The above-mentioned (C) crosslinking agent can be used alone or in combination of two or more. The content of the (C) crosslinking agent is preferably 5% to 100% by mass relative to 100 parts by mass of the above-mentioned (A) polymer, and more preferably 10% to 50% by mass. If the addition amount is 5% by mass or more, the crosslinking reaction with the (A) polymer is promoted to form a dense film with excellent curability, and therefore, a resist lower layer film with good heat resistance, dry etching resistance and film thickness uniformity can be formed. On the other hand, if the addition amount is less than 100% by mass, the generation of passivated sublimates accompanying the crosslinking reaction of the (A) polymer and the (C) crosslinking agent can be suppressed, and the generation of sublimates and the degradation of film thickness uniformity can be reduced.
[0271] [(D) Surfactant]
[0272] In order to improve the coating property in spin coating, a surfactant (D) may be added to the resist underlayer film-forming composition. As the surfactant, for example, the surfactants described in
[0142] to
[0147] in Japanese Patent Application Publication No. 2009-269953 may be used. The amount of the surfactant added is preferably 0.001 to 20 parts by mass, more preferably 0.01 to 10 parts by mass, relative to 100 parts by mass of the polymer (A).
[0273] [(E) Acid generator]
[0274] The resist underlayer film-forming composition may be a composition that generates an acid by thermal decomposition or a composition that generates an acid by light irradiation, and any of these may be added. Specifically, the materials described in paragraphs
[0061] to
[0085] of Japanese Patent Application Laid-Open No. 2007-199653 may be added, but are not limited thereto.
[0275] The acid generator may be used alone or in combination of two or more. The amount of the acid generator added is preferably 0.05 to 50 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the (A) polymer.
[0276] [(F) Plasticizer]
[0277] In addition, in order to further improve the thermal fluidity, a plasticizer (F) may be added to the resist underlayer film-forming composition. The plasticizer is not particularly limited, and plasticizers of various known systems can be widely used. As an example, low molecular weight compounds such as phthalates, adipic acid esters, phosphates, trimellitic acid esters, and citrates; polymers such as polyethers, polyesters, and polyacetal polymers described in Japanese Patent Application Laid-Open No. 2013-253227 can be illustrated. The amount of the plasticizer added is preferably 5 to 500 parts by mass, and more preferably 10 to 200 parts by mass, relative to 100 parts by mass of the polymer (A).
[0278] In addition, in addition to the above-mentioned additives, an additive (fluidity promoter) for further improving thermal fluidity can be added to the above-mentioned resist underlayer film forming composition. The above-mentioned additive is not particularly limited as long as it helps to improve thermal fluidity, impart fill characteristics and planarization characteristics. For example, it is preferred to use a liquid additive having a polyethylene glycol or polypropylene glycol structure; or a thermally decomposable polymer having a weight reduction rate of 40% by mass or more between 30°C and 250°C and a weight average molecular weight of 300 to 200,000. The thermally decomposable polymer preferably contains a repeating unit having an acetal structure represented by the following general formula (DP1) or (DP1a).
[0279]
[0280] (In the formula, R6 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. Y is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.)
[0281]
[0282] (Where R 6a Y is an alkyl group having 1 to 4 carbon atoms. a It is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, and optionally has an ether bond. n represents the average number of repeating units, and is 3 to 500.
[0283] <Pattern Formation Method>
[0284] In addition, in the present invention, as a pattern forming method using the above-mentioned resist underlayer film forming composition and based on a two-layer resist process, the following pattern forming method is provided, which is characterized in that a resist underlayer film is formed on a processed substrate by the resist underlayer film forming method of the present invention, a resist upper layer film is formed on the resist underlayer film using a photoresist material, the resist upper layer film is pattern-exposed, and then developed using a developer to form a pattern on the resist upper layer film, using the resist upper layer film with the pattern as a mask, the pattern is transferred to the resist underlayer film by dry etching, the processed substrate is processed using the resist underlayer film with the pattern as a mask, and a pattern is formed on the processed substrate.
[0285] The resist upper film in the two-layer resist process is preferably a photosensitive organic metal oxide film. The photosensitive organic metal oxide film shows resistance to etching based on oxygen-based gas, so in the two-layer resist process, it is preferred to use an etching gas mainly composed of oxygen-based gas to perform dry etching of the resist lower film using the resist upper film as a mask.
[0286] In addition, the present invention provides a method for forming a pattern on a substrate to be processed, as a method for forming a pattern based on a three-layer resist process using the resist underlayer film-forming composition, characterized in that the method comprises the following steps:
[0287] (I-1) a step of forming a resist underlayer film on a substrate to be processed by the resist underlayer film forming method of the present invention;
[0288] (I-2) a step of forming a resist intermediate film on the resist underlayer film;
[0289] (I-3) a step of forming a resist upper layer film on the resist intermediate film using a photoresist material;
[0290] (I-4) a step of exposing the resist upper layer film to pattern exposure and then developing the resist upper layer film with a developer to form a pattern on the resist upper layer film;
[0291] (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film having the pattern as a mask;
[0292] (I-6) a step of transferring the pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern is transferred as a mask; and
[0293] (I-7) A step of processing the substrate to be processed using the resist underlayer film having the pattern formed thereon as a mask to form a pattern on the substrate to be processed.
[0294] use Figure 1 , an example of a pattern forming method based on a three-layer resist process is described. First, Figure 1 As in (A), by the resist underlayer film forming method of the present invention, a resist underlayer film 3 is formed on the processed layer 2 of a processed substrate 1A including a supporting substrate 1 and a processed layer 2 formed thereon, a resist intermediate film 4 is formed on the resist underlayer film 3 using a resist intermediate film material, and a resist upper film 5 is formed on the resist intermediate film 4 using a photoresist material. Then, as Figure 1 As in (B), by pattern exposure, an exposed portion 6 is formed in the resist upper film 5. Next, the exposed portion 6 is developed using a developer, such as Figure 1 As in (C), the resist upper film 5 is formed into a resist upper film pattern 5a. Next, the resist upper film 5 having the pattern 5a is used as a mask, and dry etching is performed. Figure 1 As in (D), the silicon-containing resist intermediate film pattern 4a is transferred to the resist intermediate film 4. Next, the resist intermediate film 4 to which the pattern 4a is transferred is used as a mask, and dry etching is performed. Figure 1 As in (E), the resist underlayer film pattern 3a is transferred to the resist underlayer film 3. Then, the resist underlayer film 3 having the pattern 3a is used as a mask to process the processed layer 2 of the processed substrate 1A, as shown in FIG. Figure 1 As in (F), a pattern 2a is formed on the aforementioned substrate 1.
[0295] The silicon-containing resist intermediate film of the above-mentioned three-layer resist process shows resistance to etching based on oxygen-based gases. Therefore, in the above-mentioned three-layer resist process, it is preferred to use an etching gas with oxygen-based gas as the main body to perform dry etching of the resist lower layer film using the silicon-containing resist intermediate film as a mask.
[0296] As the silicon-containing resist intermediate film of the above-mentioned three-layer resist process, it is also preferred to use an intermediate film based on polysiloxane. By providing the silicon-containing resist intermediate film with an anti-reflection effect, reflection can be suppressed. In particular, for 193nm exposure purposes, if a material containing a large number of aromatic groups and having a high etching selectivity with the substrate is used as an organic film, the k value becomes higher and the substrate reflection becomes higher, but as a silicon-containing resist intermediate film, by having an absorption that exhibits an appropriate k value, reflection can be suppressed, and the substrate reflection can be set to less than 0.5%. As a silicon-containing resist intermediate film with an anti-reflection effect, in 248nm or 157nm exposure purposes, it is preferred to use a polysiloxane with pendant anthracene and cross-linked by acid or heat, and in 193nm exposure purposes, it is preferred to use a polysiloxane with pendant phenyl or light-absorbing groups having silicon-silicon bonds and cross-linked by acid or heat.
[0297] Furthermore, the present invention provides a pattern forming method using the resist underlayer film forming composition and based on a four-layer resist process, which comprises the following steps: forming a resist underlayer film on a substrate to be processed by the resist underlayer film forming method of the present invention; forming a silicon-containing resist interlayer film on the resist underlayer film using a silicon-containing resist interlayer film material; forming an organic antireflection film (BARC) or a close-fitting film on the silicon-containing resist interlayer film; and forming a photoresist material on the BARC or close-fitting film. A resist upper film is formed on the film, and after the resist upper film is pattern-exposed, it is developed using a developer to form a pattern on the resist upper film, using the resist upper film with the pattern as a mask, and the pattern is transferred to the BARC or the sealing film and the silicon-containing resist intermediate film using dry etching, and the silicon-containing resist intermediate film with the pattern transferred is used as a mask, and the pattern is transferred to the resist lower film using dry etching, and the resist lower film with the pattern is used as a mask to process the processed substrate to form a pattern on the processed substrate.
[0298] In addition, an inorganic hard mask can be formed to replace the silicon-containing resist intermediate film. In this case, at least the resist underlayer film forming composition of the present invention is used to form a resist underlayer film on the workpiece, an inorganic hard mask selected from silicon oxide film, silicon nitride film, and silicon oxide nitride film is formed on the resist underlayer film, a photoresist composition is used to form a resist upper film on the inorganic hard mask, a circuit pattern is formed on the resist upper film, and the inorganic hard mask is etched using the resist upper film with the pattern as a mask. The resist underlayer film is etched using the inorganic hard mask with the pattern as a mask, and further, the workpiece is etched using the resist underlayer film with the pattern as a mask to form a pattern on the workpiece, thereby forming a circuit pattern of a semiconductor device on the substrate.
[0299] As described above, when an inorganic hard mask is formed on the resist underlayer film, a silicon oxide film, a silicon nitride film, and a silicon oxide nitride film (SiON film) can be formed by using a CVD method, an ALD method, or the like. For example, a method for forming a silicon nitride film is described in Japanese Patent Application Publication No. 2002-334869 and International Publication No. 2004 / 066377. The film thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. In addition, as an inorganic hard mask, it is most preferable to use a SiON film that has a high effect as an anti-reflection film. In order to make the substrate temperature reach 300 to 500° C. when forming the SiON film, the resist underlayer film must withstand a temperature of 300 to 500° C. The resist underlayer film forming composition used in the present invention has high heat resistance and can withstand high temperatures of 300°C to 500°C. Therefore, it can be a combination of an inorganic hard mask formed by CVD or ALD and a resist underlayer film formed by spin coating.
[0300] As described above, a photoresist film as a resist upper film can be formed on an inorganic hard mask, and an organic anti-reflection film (BARC) or a close-fitting film can be formed on the inorganic hard mask by spin coating, and a photoresist film can be formed thereon. In particular, when a SiON film is used as an inorganic hard mask, the anti-reflection films of the SiON film and the BARC can suppress reflection even in liquid immersion exposure with a high NA exceeding 1.0. As another advantage of forming a BARC, there is an effect of reducing the tailing of the photoresist pattern directly above the SiON film.
[0301] In the above-mentioned pattern forming method, the resist upper layer film may be either positive or negative, and the same film as the commonly used photoresist composition may be used. In addition, the photoresist composition may contain metal atoms such as Sn, In, Ga, Ge, Al, Ce, La, Cs, Zr, Hf, Ti, Bi, Sb, and Zn. When the resist upper layer film is formed using the above-mentioned photoresist composition, it may be a spin coating method or a method of forming it by a vapor deposition process based on CVD or ALD.
[0302] When the resist upper layer is formed by spin coating, a pre-bake is performed after the resist is applied, preferably at 60 to 180° C. and for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, and post-exposure baking (PEB) and development are performed to obtain a resist pattern. It should be noted that the thickness of the resist upper layer is not particularly limited, but is preferably 10 to 500 nm, and particularly preferably 20 to 400 nm.
[0303] When the resist upper film is formed by evaporation treatment based on CVD or ALD, the resist composition is a metal oxide film with EUV sensitivity, and the metal is selected from Sn, Zr, Hf, Ti, Bi, Sb, etc., wherein Sn with excellent EUV sensitivity is preferred. The film containing metal oxide can be a photosensitive organic metal oxide film such as organic tin oxide (such as halogenated alkyl Sn, alkoxyalkyl Sn or amide alkyl Sn). Several specific examples of suitable precursors include trimethyltin chloride, dimethyltin dichloride, methyltin trichloride, tris(dimethylamino)methyltin (IV) and (dimethylamino)trimethyltin (IV).
[0304] The metal oxide film can be deposited by PECVD or PEALD using, for example, a Lam Vector (registered trademark) tool. In the ALD embodiment, the Sn oxide precursor is separated from the O precursor / plasma. The evaporation temperature is preferably in the range of 50°C to 600°C. The evaporation pressure is preferably between 100 and 6000 mTorr. The flow rate of the precursor liquid of the film containing the metal oxide (for example, an organic tin oxide precursor) can be 0.01 to 10 cmm, and the gas flow rate (CO2, CO, Ar, N2) can be 100 to 10000 sccm. Regarding plasma power, high-frequency plasma (for example, 13.56 MHz, 27.1 MHz or a higher frequency) can be used, which is 200 to 1000 W relative to a 300 mm wafer station. The evaporation thickness is preferably
[0305] Examples of the exposure light include high-energy rays having a wavelength of 300 nm or less, and specifically, excimer lasers of 248 nm, 193 nm, and 157 nm, soft X-rays of 3 to 20 nm, electron beams, and X-rays.
[0306] As a method for patterning the resist upper layer film, patterning is preferably performed by photolithography with a wavelength of 5 nm to 300 nm, direct writing with electron beams, nanoimprinting, or a combination thereof.
[0307] In addition, the development method in the above-mentioned pattern forming method is preferably set to alkali development or development with an organic solvent.
[0308] Then, etching is performed using the obtained resist pattern as a mask. The etching of the silicon-containing resist intermediate film and the inorganic hard mask in the three-layer resist process is performed using a freon-based gas and the upper resist pattern as a mask. Thus, a silicon-containing resist intermediate film pattern and an inorganic hard mask pattern are formed.
[0309] Next, the resist underlayer film is etched using the obtained silicon-containing resist intermediate film pattern and the inorganic hard mask pattern as masks. The resist underlayer film is preferably etched using an etching gas mainly containing an oxygen-based gas.
[0310] The subsequent etching of the workpiece can also be performed by conventional methods. For example, if the workpiece is SiO2, SiN, or a silicon dioxide-based low dielectric constant insulating film, the etching is performed mainly using a Freon-based gas. Regarding substrate processing, when etching is performed using a Freon-based gas, the silicon-containing resist intermediate film pattern in the three-layer resist process is stripped off while the substrate is being processed.
[0311] The resist underlayer film obtained by the resist underlayer film forming method of the present invention has a feature of being excellent in etching resistance when etching such a workpiece.
[0312] It should be noted that there is no particular limitation on the object to be processed (processed substrate), and substrates such as Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc. can be used; an object on which a processed layer is formed on the substrate (support substrate), etc. As the processed layer, various Low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si, etc. and barrier films thereof can be used, and a thickness of 50 to 10,000 nm can usually be formed, and a thickness of 100 to 5,000 nm can be formed in particular. It should be noted that when forming a film of the processed layer, objects of different materials are used for the substrate and the processed layer.
[0313] Example
[0314] Hereinafter, the present invention will be specifically described by showing synthesis examples, comparative synthesis examples, embodiments and comparative examples, but the present invention is not limited thereto. It should be noted that as molecular weight and dispersity, the weight average molecular weight (Mw) and number average molecular weight (Mn) calculated based on polystyrene conversion by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent are obtained to obtain dispersity (Mw / Mn).
[0315] Synthesis Example (A) Synthesis of polymer
[0316] Polymers (A1) to (A13) were synthesized according to the following steps. In the synthesis of polymers (A1) to (A6) and polymers (A11) to (A13), the following compound group b: (b1) to (b10) was used.
[0317]
[0318] [Synthesis Example 1] Synthesis of polymer (A1)
[0319]
[0320] Under a nitrogen atmosphere, 60.0 g of compound (b1) and 300 g of 1,2-dichloroethane were mixed, and after being uniformly dispersed at an internal temperature of 60°C, 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 400 g of 1,2-dichloroethane was added, and then the insoluble components were removed by filtration. The recovered filtrate was washed 6 times with 200 g of pure water, and the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to make a uniform solution, it was crystallized in 500 g of methanol. The precipitated crystals were separated by filtration, washed in the order of 300 g of methanol and 300 g of diisopropyl ether, and the crystals were recovered. 33.2 g of polymer (A1) was obtained by vacuum drying the recovered crystals at 70°C.
[0321] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0322] (A1): Mw=560, Mw / Mn=2.43
[0323] [Synthesis Example 2] Synthesis of polymer (A2)
[0324]
[0325] Under a nitrogen atmosphere, 30.0 g of compound (b2), 22.2 g of compound (b3) and 300 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C. Then, 55.0 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 24 hours. After cooling to room temperature, 400 g of 1,2-dichloroethane was added, and then the insoluble components were removed by filtration. The recovered filtrate was washed 6 times with 200 g of pure water, and the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to make a uniform solution, it was crystallized in 500 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and the crystals were recovered. 45.6 g of polymer (A2) was obtained by vacuum drying the recovered crystals at 70°C.
[0326] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0327] (A2): Mw=3560, Mw / Mn=1.93
[0328] [Synthesis Example 3] Synthesis of polymer (A3)
[0329]
[0330] Under a nitrogen atmosphere, 30.0 g of compound (b1), 22.8 g of compound (b4) and 260 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C. Then, 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and then the insoluble components were removed by filtration. The recovered filtrate was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 120 g of THF to the residue to make a uniform solution, it was crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed in the order of 300 g of methanol and 300 g of diisopropyl ether, and the crystals were recovered. 33.3 g of polymer (A3) was obtained by vacuum drying the recovered crystals at 70°C.
[0331] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0332] (A3): Mw=720, Mw / Mn=2.13
[0333] [Synthesis Example 4] Synthesis of polymer (A4)
[0334]
[0335] Under a nitrogen atmosphere, 30.0 g of compound (b1), 15.6 g of compound (b5) and 230 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C. Then, 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and then the insoluble components were removed by filtration. The recovered filtrate was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 120 g of THF to the residue to make a uniform solution, it was crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed in the order of 300 g of methanol and 300 g of diisopropyl ether, and the crystals were recovered. 27.3 g of polymer (A4) was obtained by vacuum drying the recovered crystals at 70°C.
[0336] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0337] (A4): Mw=680, Mw / Mn=2.27
[0338] [Synthesis Example 5] Synthesis of polymer (A5)
[0339]
[0340] Under a nitrogen atmosphere, 60.0 g of compound (b1), 4.6 g of compound (b6) and 325 g of 1,2-dichloroethane were mixed and uniformly dispersed at an internal temperature of 60°C. Then, 55.4 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and then the insoluble components were removed by filtration. The recovered filtrate was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 200 g of THF to the residue to make a uniform solution, it was crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed in the order of 300 g of methanol and 300 g of diisopropyl ether, and the crystals were recovered. 36.3 g of polymer (A5) was obtained by vacuum drying the recovered crystals at 70°C.
[0341] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0342] (A5): Mw=700, Mw / Mn=1.43
[0343] [Synthesis Example 6] Synthesis of polymer (A6)
[0344]
[0345] Under a nitrogen atmosphere, 60.0 g of compound (b4), 6.3 g of compound (b7) and 350 g of 1,2-dichloroethane were mixed, and a uniform solution was prepared at an internal temperature of 60°C. Then, 80.2 g of methanesulfonic acid was added dropwise over 1 hour, and the mixture was heated and stirred at an internal temperature of 70°C for 6 hours. After cooling to room temperature, 200 g of 1,2-dichloroethane was added, and the organic layer was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 200 g of THF to the residue to prepare a uniform solution, it was crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, and washed in the order of 300 g of methanol and 300 g of diisopropyl ether to recover the crystals. 35.5 g of polymer (A6) was obtained by vacuum drying the recovered crystals at 70°C.
[0346] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0347] (A6): Mw=730, Mw / Mn=1.38
[0348] [Synthesis Example 7] Synthesis of polymer (A7)
[0349]
[0350] Under a nitrogen atmosphere, 3.8 g of methanesulfonic acid and 30 g of dichloromethane were mixed, and after homogenizing at an internal temperature of 30°C, a mixed solution of 30.0 g of acenaphthylene and 60.0 g of dichloromethane was added dropwise over 1 hour, and heated and stirred at an internal temperature of 35°C for 24 hours. After cooling to room temperature, 300 g of toluene was added, and the mixture was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 90 g of THF to the residue to make a uniform solution, it was crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and the crystals were recovered. 28.7 g of polymer (A7) was obtained by vacuum drying the recovered crystals at 70°C.
[0351] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0352] (A7): Mw=2400, Mw / Mn=1.93
[0353] [Synthesis Example 8] Synthesis of polymer (A8)
[0354]
[0355] Under a nitrogen atmosphere, 5.0 g of methanesulfonic acid and 30.0 g of dichloromethane were mixed, and after homogenizing at an internal temperature of 30 ° C, a mixed solution of 30.0 g of indene and 60.0 g of dichloromethane was added dropwise over 1 hour, and heated and stirred at an internal temperature of 35 ° C for 24 hours. After cooling to room temperature, 300 g of toluene was added, and washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding THF90 g to the residue to make a uniform solution, it was crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and the crystals were recovered. By vacuum drying the recovered crystals at 70 ° C, 26.9 g of polymer (A8) was obtained.
[0356] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0357] (A8): Mw=2500, Mw / Mn=1.83
[0358] [Synthesis Example 9] Synthesis of polymer (A9)
[0359]
[0360] Under a nitrogen atmosphere, 37.5 g of propylene glycol monomethyl ether acetate (PGMEA) was stirred at 80°C, and then 50.0 g of acenaphthylene, a mixture of 82.5 g of PGMEA, and a mixture of 3.8 g of dimethyl 2,2-azobis(2-methylpropionate) and 30.0 g of PGMEA were added simultaneously and separately over 2 hours. After further heating and stirring for 24 hours, the mixture was cooled to room temperature. The reaction solution was added dropwise to 750 g of methanol to crystallize the polymer. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and the crystals were recovered. 48.3 g of polymer (A9) was obtained by vacuum drying the recovered crystals at 70°C.
[0361] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0362] (A9): Mw=4100, Mw / Mn=1.73
[0363] [Synthesis Example 10] Synthesis of polymer (A10)
[0364]
[0365] Under a nitrogen atmosphere, 5.7 g of methanesulfonic acid and 29.5 g of dichloromethane were mixed, and after homogenizing at an internal temperature of 30°C, a mixed solution of 15.0 g of acenaphthylene, 6.9 g of indene, 7.6 g of 9-vinylcarbazole, and 59.0 g of dichloromethane was added dropwise over 1 hour, and heated and stirred at an internal temperature of 35°C for 24 hours. After cooling to room temperature, 300 g of toluene was added, and the mixture was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 90 g of THF to the residue to make a uniform solution, it was crystallized in 600 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and the crystals were recovered. 27.9 g of polymer (A10) was obtained by vacuum drying the recovered crystals at 70°C.
[0366] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0367] (A10): Mw=4000, Mw / Mn=2.15
[0368] [Synthesis Example 11] Synthesis of polymer (A11)
[0369]
[0370] Under a nitrogen atmosphere, 200 g of 1,2-dichloroethane was added to 30.0 g of compound (b8) to prepare a uniform solution at an internal temperature of 50°C. 15.8 g of methanesulfonic acid was slowly added, and the mixture was reacted at an internal temperature of 70°C for 8 hours. After cooling to room temperature, 500 g of toluene was added, and the mixture was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to prepare a uniform solution, and then crystallized in 300 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol, and the crystals were recovered. 25.6 g of the polymer (A11) represented by the above formula was obtained by vacuum drying the recovered crystals at 70°C.
[0371] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC measurement, the following results were obtained.
[0372] (A11): Mw=2600, Mw / Mn=1.68
[0373] [Synthesis Example 12] Synthesis of polymer (A12)
[0374]
[0375] Under a nitrogen atmosphere, 2.75 g of compound (b7), 30.0 g of compound (b8) and 200 g of 1,2-dichloroethane were added to prepare a uniform solution at an internal temperature of 50°C. 15.8 g of methanesulfonic acid was slowly added, and the mixture was reacted at an internal temperature of 70°C for 8 hours. After cooling to room temperature, 500 g of toluene was added, and the mixture was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to prepare a uniform solution, it was crystallized in 300 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol, and the crystals were recovered. By vacuum drying the recovered crystals at 70°C, 25.4 g of the polymer (A12) represented by the above formula was obtained.
[0376] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC measurement, the following results were obtained.
[0377] (A12): Mw=1420, Mw / Mn=1.53
[0378] [Synthesis Example 13] Synthesis of polymer (A13)
[0379]
[0380] Under a nitrogen atmosphere, 100 g of 1,2-dichloroethane was added to 10.0 g of compound (b9) to prepare a uniform solution at an internal temperature of 50°C. 15.8 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 4 hours. Thereafter, after cooling to an internal temperature of 50°C, a mixed solution of 13.7 g of compound (b10) and 100 g of 1,2-dichloroethane, which had been homogenized in advance, was slowly added dropwise, and the temperature was raised to an internal temperature of 70°C again, and the reaction was carried out for 8 hours. After cooling to room temperature, 500 g of toluene was added, and the mixture was washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to prepare a uniform solution, it was crystallized in 300 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol, and the crystals were recovered. By vacuum drying the recovered crystals at 70°C, 18.7 g of the polymer (A13) represented by the above formula was obtained.
[0381] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC measurement, the following results were obtained.
[0382] (A13): Mw=2930, Mw / Mn=1.61
[0383] [Synthesis of Compounds for Comparative Examples]
[0384] In the synthesis of the comparative example compounds (R2), (R3) and (R4), the compound group c shown below: (c1) to (c6) was used.
[0385]
[0386]
[0387] [Comparative Synthesis Example 1] Synthesis of Compound (R1) for Comparative Example
[0388]
[0389] Under a nitrogen atmosphere, 15.6 g of 2-phenylphenol, 19.1 g of 9-anthracene methanol, 12.3 g of divinylbenzene, 30 g of cyclopentyl methyl ether (CPME) and 110 g of diethylene glycol dimethyl ether were added and stirred at room temperature to make them uniformly dispersed. Thereafter, 1.14 g of trifluorosulfonic acid was slowly added, and after further stirring for 5 minutes to make a uniform solution, the reaction was carried out for 4 hours in an oil bath at 140 ° C while removing the generated water from the reaction system. Cool to room temperature, dilute with 250 g of CPME and transfer to a separatory funnel, wash with ultrapure water 4 times, and then dry the organic layer under reduced pressure. 120 g of CPME was added to the residue, and the polymer was crystallized with 500 g of hexane. The precipitated crystals were separated by filtration, washed twice with 200 g of hexane, and the crystals were recovered. The recovered crystals were vacuum dried at 70 ° C to obtain a comparative example compound (R1).
[0390] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0391] (R1): Mw=1960, Mw / Mn=1.57
[0392] [Comparative Synthesis Example 2] Synthesis of Compound (R2) for Comparative Example
[0393]
[0394] In a nitrogen atmosphere, 80.0 g of the epoxy compound (c1), 51.0 g of the modifying agent (c2) and 600 g of 2-methoxy-1-propanol were added to form a uniform solution at 100°C, and then 5.7 g of benzyltriethylammonium chloride was added and stirred at 120°C for 12 hours. After cooling to room temperature, 1,500 g of methyl isobutyl ketone was added, and the organic layer was washed 5 times with 300 g of pure water. The organic layer was dried under reduced pressure to obtain a comparative example compound (R2).
[0395] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0396] (R2): Mw=900, Mw / Mn=1.04
[0397] [Comparative Synthesis Example 3] Synthesis of Compound (R3) for Comparative Example
[0398]
[0399] Under a nitrogen atmosphere, 20 g of 9-fluorenone (c3), 230 g of 9,9-bis(4-hydroxyphenyl)fluorene (c4) and dichloromethane (1,040 g) were added to form a uniform solution at 40°C, and trifluoromethanesulfonic acid (9 g) and 3-mercaptopropionic acid (0.6 g) dissolved in dichloromethane (20 g) were added, and stirred at 40°C for 4 hours. After cooling to room temperature, the organic layer was washed 5 times with 300 g of pure water. The organic layer was dried under reduced pressure to obtain a comparative example compound (R3).
[0400] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0401] (R3): Mw=680, Mw / Mn=1.26
[0402] [Comparative Synthesis Example 4] Synthesis of Compound (R4) for Comparative Example
[0403]
[0404] Under nitrogen atmosphere, add the comparative example compound R3 (20 g), potassium carbonate (32 g), and acetone (62 g) obtained in comparative synthesis example 3, and after making a uniform solution at 56° C., slowly add 3-bromo-1-propyne (28 g) to the reactor and stir at 56° C. for 3 hours. Cool to room temperature, remove excess potassium carbonate and salt by filtration, and wash the precipitate with acetone. Wash the organic layer with 300 g of pure water 5 times. The organic layer is dried under reduced pressure to obtain a comparative example compound (R4).
[0405] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0406] (R4): Mw=1,040, Mw / Mn=1.38
[0407] [Comparative Synthesis Example 5] Synthesis of Compound (R5) for Comparative Example
[0408]
[0409] To a 200 mL flask, 15.2 g of acenaphthylene, 3.3 g of 4-hydroxystyrene, and 60 g of 1,2-dichloroethane as a solvent were added. 1 g of boron trifluoride as a polymerization initiator was added, and the mixture was heated to 60° C. and reacted for 25 hours. 1 L of methanol and 500 g of water were added to the reaction solution to precipitate a polymer, and the obtained white solid was filtered and dried to obtain 12 g of a polymer (Comparative Example Compound (R5)).
[0410] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0411] (R5): Mw=8800, Mw / Mn=1.82
[0412] [Comparative Synthesis Example 6] Synthesis of Compound (R6) for Comparative Example
[0413]
[0414] 41.2 g of tertiary alcohol (c6) and 160 g of dichloromethane were mixed, 19.2 g of methanesulfonic acid was slowly added dropwise, and the mixture was heated under reflux for 8 hours. After cooling to room temperature, 250 g of toluene was added, and the mixture was washed with water and concentrated under reduced pressure to obtain 37.6 g of the comparative example compound (R6).
[0415] When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, the following results were obtained.
[0416] (R6): Mw=1850, Mw / Mn=1.26
[0417] [Synthesis Example: (C) Synthesis of Cross-linking Agent]
[0418] [Synthesis Example 15] Synthesis of Compound (C1)
[0419]
[0420] Under a nitrogen atmosphere, add 500 mL of a 2.67 M hexane solution of n-butyl lithium to a mixture of 219 g of bis(4-bromophenyl) ether and 1000 mL of tert-butyl methyl ether cooled to -20°C, and stir at -20°C for 20 minutes. Add 229 g of 9-fluorenone, slowly warm to room temperature, and stir at room temperature for 4 hours. Add water to stop the reaction. After washing with water and concentrating under reduced pressure, add hexane, filter out the generated solid, wash with hexane, and dry under reduced pressure to obtain 293 g of compound (C1).
[0421] (C1): Mw=540, Mw / Mn=1.02
[0422] [Synthesis Example 16] Synthesis of Compound (C2)
[0423]
[0424] Under a nitrogen atmosphere, 30.0 g of compound (C1) and 172.8 g of 1-butanol were made into a suspension at an internal temperature of 80 ° C. 16.8 g of methanesulfonic acid was slowly added and the reaction was carried out for 6 hours at an internal temperature of 100 ° C. After cooling in an ice bath to precipitate crystals, the precipitated crystals were separated by filtration, washed twice with 200 g of butanol, washed three times with 200 g of diisopropyl ether, and recovered. 34.2 g of compound (C2) was obtained by vacuum drying the recovered crystals at 60 ° C. When the weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were obtained by GPC, the following results were presented.
[0425] (C2): Mw=640, Mw / Mn=1.01
[0426] [Preparation of Resist Underlayer Film-Forming Composition (UDL-1)]
[0427] The polymer (A1) as a resist underlayer film-forming compound was dissolved in a mixed solvent of propylene glycol monomethyl ether acetate (PGMEA) and cyclohexanone (CyHO) containing 0.5 mass % of a surfactant FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) at the ratio shown in Table 2. The obtained solution was filtered with a 0.02 μm membrane filter to prepare a resist underlayer film-forming composition (UDL-1).
[0428] [Preparation of Resist Underlayer Film-forming Compositions (UDL-2 to 16) and Resist Underlayer Film-forming Compositions for Comparative Examples (UDL-1 to 6 for Comparative Examples)]
[0429] Resist underlayer film-forming compositions (UDL-2 to 16) and resist underlayer film-forming compositions for comparative examples (UDL-1 to 6 for comparative examples) were prepared in the same manner as for the resist underlayer film-forming composition (UDL-1), except that the types and contents of the components were as shown in Table 2. In Table 2, "-" indicates that the corresponding component was not used. The acid generator (TAG) used the following formula (E1), and the fluidity promoter used the following formula (G1).
[0430] [Acid generator]
[0431] The thermal acid generator (E1) used in the resist underlayer film-forming composition is shown below.
[0432]
[0433] [Flowability enhancer]
[0434] Table 1 shows the fluidity improver (G1) used in the resist underlayer film-forming composition.
[0435] [Table 1]
[0436]
[0437] [Table 2]
[0438]
[0439] [Example 1 and Comparative Example 1: Evaluation of dry etching resistance]
[0440] The resist underlayer film-forming compositions prepared above (UDL-1 to 16, comparative example UDL-1 to 6) were coated on silicon substrates respectively and fired at 250°C for 60 seconds. Thereafter, the film thickness from the center of the substrate to the periphery was measured, and the average film thickness (a [nm]) was calculated. Next, etching was performed using CF4 gas under the following conditions using an etching device Telius manufactured by Tokyo Electron Limited, and the film thickness b was measured. The film thickness etched within 1 minute was calculated from the film thickness (film thickness a - film thickness b) etched within a specified time using CF4 gas as the etching rate A (nm / min). The results are shown in Table 3.
[0441] Separately from the above, compositions for forming a resist underlayer film (UDL-1 to 16, comparative example UDL-1 to 6) were coated on silicon substrates and heated at 250°C for 60 seconds. Thereafter, plasma treatment was performed under the following plasma treatment conditions to form a resist underlayer film, and the film thickness c was measured. Next, etching was performed using CF4 gas under the following conditions using an etching apparatus Telius manufactured by Tokyo Electron Limited, and the film thickness d was measured. The film thickness etched in 1 minute was calculated from the film thickness etched in a specified time using CF4 gas (film thickness c - film thickness d) to be the etching rate B (nm / min).
[0442] The smaller the number of the etching rate, the better the etching resistance to CF4 gas.
[0443] The etching resistance of the cured film (resist underlayer film) after additional plasma treatment was compared with that of the underlayer film precursor film obtained by sintering at 250°C, and the effect of improving the etching resistance by additional plasma treatment was calculated (etching rate A (nm / min) - etching rate B (nm / min)).
[0444] The etching conditions are as follows.
[0445] Dry etching conditions based on CF4 gas
[0446] Chamber pressure: 100mT
[0447] RF power (upper): 500W
[0448] RF power (lower): 400W
[0449] CF4 gas flow rate: 300sccm
[0450] Time: 30 seconds
[0451] Additional treatment conditions (plasma treatment)
[0452] Each substrate heated at 250° C. for 60 seconds was subjected to plasma treatment under the following conditions using an etching apparatus Telius manufactured by Tokyo Electron Limited.
[0453] Plasma treatment conditions
[0454] Chamber pressure: 100mT
[0455] RF power (upper): 100W
[0456] RF power (lower): 3500W
[0457] H2 gas flow rate: 200sccm
[0458] Time: 20 seconds
[0459] [Table 3]
[0460]
[0461] As shown in Table 3, in Examples 1-1 to 1-16 obtained using the resist underlayer film forming composition (UDL-1 to 16), the additional treatment of plasma irradiation can significantly improve the dry etching resistance to CF4 gas. The resist underlayer film forming composition used in Examples 1-1 to 1-16 as embodiments of the present invention does not contain a hydroxyl group and an organic group represented by the above general formula (1) in the repeating unit of the polymer. Therefore, it is believed that the carbon bonds of the resist underlayer film precursor film are separated and re-bonded by plasma irradiation, and it is easy to reconstruct it in the form of a cured film having a diamond-like carbon structure, that is, a resist underlayer film, which shows excellent dry etching resistance. On the other hand, the improvement in dry etching resistance achieved by additional treatment of Comparative Examples UDL-1 to 6 is as small as 10 nm / min or less. Comparative Example UDL-1 to -6 contain hydroxyl groups or organic groups represented by the general formula (1) in the repeating units of the polymers. Therefore, it is presumed that not only separation and recombination of carbon bonds occur, but also crosslinking reactions occur competitively, and the film modification by plasma irradiation is not fully performed.
[0462] UDL-5 contains hydroxyl groups in the terminal structure of the polymer, but does not contain hydroxyl groups in the repeating units of the polymer. Therefore, it is presumed that the carbon bonds are separated and re-bonded during plasma irradiation without being hindered by the cross-linking reaction, and the film is modified to exhibit excellent dry etching resistance.
[0463] [Example 2 and Comparative Example 2: Evaluation of Landfill Characteristics]
[0464] The above-mentioned resist underlayer film forming compositions (UDL-1 to 16 and comparative examples UDL-1 to 6) were coated on SiO2 wafer substrates having dense line & space patterns (line width of 60nm, line depth of 100nm, center distance between two adjacent lines (120nm)). Then, the coating was fired at 250°C for 60 seconds to form a resist underlayer film precursor film with a film thickness of 100nm. The substrate used was Figure 2 A base substrate 7 (SiO2 wafer substrate) having a dense line & space pattern as shown in (G) (top view) and (H) (cross-sectional view). Next, under the same additional processing conditions as in the above-mentioned dry etching resistance evaluation, plasma irradiation treatment was performed respectively, and the cross-sectional shape of each obtained wafer substrate was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd. to confirm whether there are pores (voids) inside the resist underlayer film that fills between the lines. The results are shown in Table 4. When a composition for forming a resist underlayer film having poor filling characteristics is used, in this evaluation, pores are generated inside the resist underlayer film that fills between the lines. When a composition for forming a resist underlayer film having good filling characteristics is used, in this evaluation, as Figure 2 As shown in (I) of FIG. 1 , the resist underlayer film 8 having no voids is filled inside the resist underlayer film that fills the spaces between the lines of the base substrate 7 having a dense line & space pattern.
[0465] [Table 4]
[0466]
[0467] As shown in Table 4, the resist underlayer film forming composition (UDL-1 to 16) used in Example 2 of the present invention can fill the dense line & space pattern without generating voids even after the additional treatment of plasma irradiation, and it can be confirmed that it has good filling characteristics. It was also confirmed that there was no problem with the filling characteristics of Comparative Examples UDL-1 to 6.
[0468] [Example 3 and Comparative Example 3: Pattern Formation Method]
[0469] The above-mentioned compositions for forming a resist underlayer film (UDL-1 to 16 and comparative examples UDL-1 to 6) were coated on a silicon wafer substrate on which a SiO2 film having a groove pattern (groove width of 10 μm and groove depth of 0.10 μm) was formed, and fired at 250°C for 60 seconds in the atmosphere to form a resist underlayer film precursor film with a film thickness of 100 nm. Thereafter, the same plasma irradiation treatment as the above-mentioned dry etching resistance evaluation was performed. A resist intermediate layer material (SOG-1) containing silicon atoms was coated thereon, and baked at 220°C for 60 seconds to form a resist intermediate layer film with a film thickness of 20 nm, and an ArF single-layer resist material for a resist upper layer film material was coated thereon, and baked at 105°C for 60 seconds to form a photoresist film with a film thickness of 100 nm. The liquid immersion protective film material (TC-1) was applied on the photoresist film and baked at 90° C. for 60 seconds to form a protective film with a film thickness of 50 nm.
[0470] The resist intermediate layer material (SOG-1) containing silicon atoms was prepared according to the following steps. The polymer represented by the ArF silicon-containing intermediate film polymer (SiP1) and the crosslinking catalyst (CAT1) were dissolved in propylene glycol monoethyl ether containing 0.1% by mass of FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) as an organic solvent in the proportions shown in Table 5. The obtained solution was filtered using a fluororesin filter with a pore size of 0.1 μm to prepare the resist intermediate layer material (SOG-1) containing silicon atoms.
[0471] [Table 5]
[0472]
[0473] The structural formulas of the ArF silicon-containing interlayer polymer (SiP1) and the crosslinking catalyst (CAT1) used are shown below.
[0474]
[0475] The resist upper film material (ArF single-layer resist material) was prepared according to the following steps. The polymer (RP1), the acid generator (PAG1) and the alkaline compound (Amine1) were dissolved in a solvent containing 0.1% by mass of propylene glycol monoethyl ether acetate (PGMEA) containing a surfactant FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) in the proportions shown in Table 6. Then, the resulting solution was filtered using a 0.1 μm fluororesin filter. Thus, a single-layer resist material for ArF was prepared.
[0476] [Table 6]
[0477]
[0478] The polymer (RP1), the acid generator (PAG1), and the basic compound (Amine1) used in the resist upper layer film material (ArF single-layer resist material) are shown below.
[0479]
[0480]
[0481] The liquid immersion protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent at the ratio shown in Table 7 and filtering the solution through a 0.1 μm fluororesin filter.
[0482] [Table 7]
[0483]
[0484] The polymer (PP1) used for the liquid immersion protective film material (TC-1) is shown below.
[0485]
[0486] Next, the resist upper layer film was pattern-exposed using an ArF immersion exposure apparatus (manufactured by Nikon Corporation; NSR-S610C, NA of 1.30, σ of 0.98 / 0.78, 35-degree dipole s-polarized illumination, 6% halftone phase shift mask). Next, baking (PEB) was performed at 100°C for 60 seconds, and development was performed for 30 seconds using a 2.38% by mass tetramethylammonium hydroxide (TMAH) aqueous solution. Thus, a 1:1 positive line and space pattern (resist pattern) of 45 nm was obtained.
[0487] Next, the resist intermediate layer material (SOG-1) containing silicon atoms was etched by dry etching using an etching apparatus Telius manufactured by Tokyo Electron Limited using the resist pattern as a mask to form a hard mask pattern (SOG-1 pattern).
[0488] Next, the resist underlayer film is etched using the obtained SOG-1 pattern as a mask to form a resist underlayer film pattern.
[0489] Then, the SiO2 film was etched using the obtained resist underlayer film pattern as a mask. The etching conditions were as follows.
[0490] Conditions for transferring a resist pattern to a resist intermediate layer material containing silicon atoms (SOG-1).
[0491] Chamber pressure: 50mT
[0492] RF power (upper): 500W
[0493] RF power (lower): 300W
[0494] CF4 gas flow rate: 150sccm
[0495] CHF3 gas flow rate: 50sccm
[0496] Time: 15 seconds
[0497] Conditions for transferring a resist intermediate layer material (SOG-1) pattern containing silicon atoms to a resist underlayer film.
[0498] Chamber pressure: 10mT
[0499] RF power (upper): 1,000W
[0500] RF power (lower): 300W
[0501] CO2 gas flow rate: 320sccm
[0502] N2 gas flow rate: 80sccm
[0503] Time: 55sec
[0504] Conditions for transferring the resist underlayer film pattern to the SiO2 film.
[0505] Chamber pressure: 100mT
[0506] RF power (upper): 500W
[0507] RF power (lower): 300W
[0508] CF4 gas flow rate: 150sccm
[0509] CHF3 gas flow rate: 30sccm
[0510] O2 gas flow rate: 10sccm
[0511] Time: 130 seconds
[0512] Table 8 shows the results of observing the pattern cross section of the pattern formed on the SiO 2 film using an electron microscope (S-4700) manufactured by Hitachi, Ltd.
[0513] [Table 8]
[0514]
[0515] As shown in Table 8, in Examples 3-1 to 3-16 in which a resist underlayer film was formed by using any of the resist underlayer film-forming compositions (UDL-1 to 16) and the resist underlayer film-forming method of the present invention, in any case, the resist upper film pattern was finally well transferred to the substrate, and it was confirmed that the resist underlayer film-forming method of the present invention is applicable to microfabrication based on the multilayer resist method. On the other hand, in Comparative Examples 3-1 to 3-6 obtained by using Comparative Examples UDL-1 to 6, which were confirmed to have insufficient etching resistance compared with the resist underlayer film-forming method of the present invention by the above-mentioned etching resistance evaluation, the pattern shape after substrate transfer etching was a vertical shape, but LWR degradation after substrate processing was observed.
[0516] In summary, the resist underlayer film forming method of the present invention can form a resist underlayer film that exhibits excellent dry etching resistance during substrate processing by plasma irradiation, and is therefore extremely useful in the next generation of micro-processing technology. In addition, it is clear that the pattern forming method of the present invention using the same can form a fine pattern with high precision even if the object to be processed is a substrate with a height difference.
[0517] This specification includes the following aspects.
[0518] [1] A method for forming a resist underlayer film, characterized in that it is a method for forming a resist underlayer film on a substrate, comprising the following steps:
[0519] (i) a step of applying a resist underlayer film-forming composition comprising (A) a polymer and an organic solvent onto the substrate to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. to 800° C. for 10 seconds to 7,200 seconds to cure the coating film, thereby forming an underlayer film precursor film; and
[0520] (ii) a step of curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film,
[0521] As the polymer (A), an aromatic ring-containing resin is used which does not contain a hydroxyl group and an organic group represented by the following general formula (1) in the repeating unit constituting the polymer.
[0522]
[0523] (In the above general formula (1), p is 0 or 1, and * is a bonding part.)
[0524] [2] The method for forming a resist underlayer film according to [1], wherein the aromatic ring-containing resin used is the polymer (A) containing a structure selected from the group consisting of structures represented by the following formula (1-1).
[0525]
[0526] [3] The method for forming a resist underlayer film according to [1] or [2], characterized in that the aforementioned (A) polymer has any of the structural units represented by the following general formulas (A-1), (A-2), (A-3), (A-4) and (A-5).
[0527]
[0528] (In the above general formula (A-1), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1).)
[0529]
[0530] (In the above general formula (A-2), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms which does not contain a hydroxyl group and an organic group represented by the above general formula (1); Ar2 is a fused aromatic ring different from Ar1, which is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms which does not contain a hydroxyl group and an organic group represented by the above general formula (1).)
[0531]
[0532] (In the above general formula (A-3), R1 is any of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms.)
[0533]
[0534] (In the above general formula (A-4), R2 is any of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms.)
[0535]
[0536] (In the above general formula (A-5), R1 represents a hydrogen atom, or a monovalent organic group having 1 to 50 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1), and Ar3 and Ar4 are each an unsubstituted benzene ring or a naphthalene ring.)
[0537] [4] The method for forming a resist underlayer film according to any one of [1] to [3], wherein the polymer (A) is a polymer having a molecular weight of 300 to 5,000 in terms of polystyrene as determined by gel permeation chromatography.
[0538] [5] The method for forming a resist underlayer film according to any one of [1] to [4], characterized in that a composition further comprising one or more of (C) a crosslinking agent, (D) a surfactant, (E) an acid generator and (F) a plasticizer is used as the composition for forming the resist underlayer film.
[0539] [6] The method for forming a resist underlayer film according to [5], characterized in that as the aforementioned (C) cross-linking agent, a cross-linking agent having a structure represented by the following general formula (C-1) is used.
[0540]
[0541] (In the above general formula (C-1), W1 and W2 are each a benzene ring or a naphthalene ring which may have a substituent, R2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any of the groups represented by the following general formula (2).)
[0542]
[0543] [7] The method for forming a resist underlayer film according to any one of [1] to [6] is characterized in that in the aforementioned step (ii), the aforementioned plasma irradiation is carried out in an atmosphere of N2, NF3, H2, fluorocarbons, rare gases or a mixture of any of them.
[0544] [8] The method for forming a resist underlayer film according to any one of [1] to [7], characterized in that in the step (i), the heat treatment is performed in an atmosphere having an oxygen concentration of not less than 1% and not more than 21%.
[0545] [9] The method for forming a resist underlayer film according to any one of [1] to [7], wherein in the step (i), the heat treatment is performed in an atmosphere having an oxygen concentration of less than 1%.
[0546]
[10] A method for forming a pattern, characterized in that it is a method for forming a pattern on a processed substrate, comprising the following steps:
[0547] (I-1) forming a resist underlayer film on a substrate to be processed by the resist underlayer film forming method described in any one of [1] to [9];
[0548] (I-2) a step of forming a resist intermediate film on the resist underlayer film;
[0549] (I-3) a step of forming a resist upper layer film on the resist intermediate film using a photoresist material;
[0550] (I-4) a step of exposing the resist upper layer film to pattern exposure and then developing the resist upper layer film with a developer to form a pattern on the resist upper layer film;
[0551] (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film having the pattern as a mask;
[0552] (I-6) a step of transferring the pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern is transferred as a mask; and
[0553] (I-7) A step of processing the substrate to be processed using the resist underlayer film having the pattern formed thereon as a mask to form a pattern on the substrate to be processed.
[0554] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are examples, and any technical solutions having substantially the same structure and exerting the same effects as the technical ideas described in the claims of the present invention fall within the technical scope of the present invention.
Claims
1. A method for forming a resist underlayer film, characterized in that: The invention relates to a method for forming a resist underlayer film on a substrate, which comprises the following steps: (i) a step of applying a resist underlayer film-forming composition comprising (A) a polymer and an organic solvent onto the substrate to obtain a coating film, and subjecting the coating film to a heat treatment at a temperature of 100° C. to 800° C. for 10 seconds to 7,200 seconds to cure the coating film, thereby forming an underlayer film precursor film; and (ii) a step of curing the underlayer film precursor film by plasma irradiation to form a resist underlayer film, As the polymer (A), an aromatic ring-containing resin is used which does not contain a hydroxyl group and an organic group represented by the following general formula (1) in the repeating units constituting the polymer. In the above general formula (1), p is 0 or 1, and * is a bonding portion.
2. The resist underlayer film forming method according to claim 1, wherein: The (A) polymer containing the aromatic ring-containing resin includes a structure selected from the group consisting of structures represented by the following formula (1-1), 3. The resist underlayer film forming method according to claim 1, wherein: The polymer (A) has any of the structural units represented by the following general formulae (A-1), (A-2), (A-3), (A-4) and (A-5), In the general formula (A-1), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group and an organic group represented by the general formula (1) as a substituent, In the general formula (A-2), Ar1 is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group and an organic group represented by the general formula (1); Ar2 is a fused aromatic ring different from Ar1, which is an unsubstituted fused aromatic ring, or a fused aromatic ring containing as a substituent a divalent organic group having 1 to 20 carbon atoms and not containing a hydroxyl group and an organic group represented by the general formula (1); In the above general formula (A-3), R1 is any one of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms. In the above general formula (A-4), R2 is any one of a hydrogen atom, a halogen atom, and a linear hydrocarbon group, a branched hydrocarbon group, and a cyclic hydrocarbon group having 1 to 20 carbon atoms. In the above general formula (A-5), R1 represents a hydrogen atom or a monovalent organic group having 1 to 50 carbon atoms and not containing a hydroxyl group and an organic group represented by the above general formula (1), and Ar3 and Ar4 are each an unsubstituted benzene ring or a naphthalene ring.
4. The resist underlayer film forming method according to claim 1, wherein: As the (A) polymer, a polymer having a molecular weight of 300 to 5,000 in terms of polystyrene based on gel permeation chromatography is used.
5. The resist underlayer film forming method according to claim 1, wherein: As the resist underlayer film-forming composition, a composition further containing one or more of (C) a crosslinking agent, (D) a surfactant, (E) an acid generator, and (F) a plasticizer is used.
6. The resist underlayer film forming method according to claim 5, wherein: As the crosslinking agent (C), a crosslinking agent having a structure represented by the following general formula (C-1) is used: In the above general formula (C-1), W1 and W2 are each a benzene ring or a naphthalene ring which may have a substituent, R2 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and X is any of the groups represented by the following general formula (2).
7. The resist underlayer film forming method according to claim 1, wherein: In the step (ii), the plasma irradiation is performed in an atmosphere of N2, NF3, H2, a fluorocarbon, a rare gas, or a mixture of any of them.
8. The resist underlayer film forming method according to any one of claims 1 to 7, wherein: In the step (i), the heat treatment is performed in an atmosphere having an oxygen concentration of 1% to 21%.
9. The resist underlayer film forming method according to any one of claims 1 to 7, wherein: In the step (i), the heat treatment is performed in an atmosphere having an oxygen concentration of less than 1%.
10. A pattern forming method, characterized in that: The method is a method for forming a pattern on a processed substrate, comprising the following steps: (I-1) a step of forming a resist underlayer film on a substrate to be processed by the resist underlayer film forming method according to any one of claims 1 to 7; (I-2) a step of forming a resist intermediate film on the resist underlayer film; (I-3) a step of forming a resist upper layer film on the resist intermediate film using a photoresist material; (I-4) a step of exposing the resist upper layer film to pattern exposure and then developing the resist upper layer film with a developer to form a pattern on the resist upper layer film; (I-5) a step of transferring the pattern to the resist intermediate film by dry etching using the resist upper layer film having the pattern formed thereon as a mask; (I-6) a step of transferring the pattern to the resist underlayer film by dry etching using the resist intermediate film to which the pattern is transferred as a mask; as well as (I-7) A step of processing the substrate to be processed using the resist underlayer film having the pattern formed thereon as a mask to form a pattern on the substrate to be processed.
Citation Information
Patent Citations
Sankabutsuatsudenzairyo
JP1982046670B2
Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof
JP2002334869A
Pattern forming method, and material for forming underlayer film
JP2004205685A
Photoresist underlayer film forming material and pattern forming method
JP2007199653A
New photoacid generator, resist material using the same, and pattern forming method
JP2009269953A